Genome-wide association study of mature cow size traits in American Angus cattle - Ayooluwa O. Ojo; Henrique A. Mulim; Milena A. F. Campos; André Garcia; Kelli Retallick-Riley; Pablo A. S. Fonseca; Hinayah R. Oliveira (Mammalian Genome, 2026)
Mature cow weight (MWT), height (MHT), and body condition score (BCS) are economically important traits that significantly influence cowherd profitability by affecting maintenance feed requirements, which is the largest component of production costs. This study aimed to identify genomic regions, candidate genes, and pleiotropic variants associated with mature cow size traits in American Angus cattle, and to characterize their related gene ontology terms and metabolic pathways. The dataset provided by the American Angus Association comprised 434,746 MWT records from 222,907 animals; 213,875 MHT records from 112,987 animals; and 382,156 BCS records from 209,696 animals. Of these, 45,606 cows were genotyped and imputed to a common marker density of 54,609 markers. A final dataset of 51,410 SNPs from 45,452 animals remained after quality control for further analyses. The single-step genome-wide association study (ssGWAS) method was used in the analyses. Significant associations for mature cow size were detected on BTA7, BTA14, and BTA20, overlapping with previously reported QTLs for growth, feed efficiency, and carcass traits. Candidate genes such as FBXO32 , STC2 , DUSP1 , CREBRF , LAP3 , and PENK were found to be related to muscle development, skeletal growth, lipid metabolism, and energy regulation. The genes FBXO32 , NTAQ1 , ATAD2 , DUSP1 , ERGIC1 , RPL26L1 , ATP6V0E1 , CREBRF , BNIP1 , NKX2-5 , and STC2 emerged as candidate genes exhibiting pleiotropic effects on mature cow size traits. Pathway enrichment highlighted the roles of insulin/IGF1R signaling, fibroblast growth factor receptors cascades, and mitogen-activated protein kinase pathways in MWT and MHT, while for BCS, only RHOD GTPase cycle was enriched. Pleiotropy-based analysis of regions affecting mature cow size traits identified shared genomic loci, and subsequent pathway analysis revealed G protein signaling as a common regulatory mechanism linking energy balance, adiposity, and growth. These results contribute to a better understanding of the genomic regions associated with mature cow size traits in Angus cattle.

Examining the Nuna-Rodinia supercontinent cycle in East Antarctica and testing correlations to the southwest United States: evidence from the Read Group (Shackleton Range) and the Nimrod Complex - Joe H. Metcalfe; Teal R. Riley; Michael J. Flowerdew; Nicholas J. Gardiner; Sebastian Fischer; Ian L. Millar; Joshua M. Garber; Maurice Brodbeck; David van Acken; Cristina Talavera; Heejin Jeon; Martin J. Whitehouse (Precambrian Research, 2026)

Benthic primary producers affect pelagic nitrogen fixation by influencing benthic nutrient fluxes in a shallow lake - K. Riley Book; Emily L. Adler; Jamieson C. Botsch; Ian S. Hart; Árni Einarsson; Anthony R. Ives (Aquatic Ecology, 2026)
Nutrient supply is an important determinant of N fixation rates in pelagic cyanobacteria. In shallow aquatic ecosystems, benthic primary producers can affect nutrient release from the sediment to the pelagic zone, yet the relationship between benthic primary producers and pelagic N fixation is not well understood. Here, we explore the effect of benthic primary producers on benthic nutrient fluxes and pelagic N fixation rates in shallow, eutrophic Lake Mývatn, Iceland. In paired benthic nutrient flux and pelagic N fixation assays, we showed that sites with increased benthic phosphate release were associated with increased pelagic N fixation. In turn, during assays of flux rates, benthic phosphate release was negatively associated with dissolved oxygen concentrations at the sediment–water interface, which was positively associated with benthic primary producer abundances. Together, these relationships suggest that benthic primary producers influence variation in within-lake pelagic N fixation via their effects on benthic nutrient flux rates.

Individual Trees Respond to 40 Years of Climate Change Through Leaf Functional Trait Acclimation - Riley P. Fortier; Rodolfo Vásquez Martínez; Rocío Del Pilar Rojas Gonzalez; Rachel Collins; Luis Valenzuela Gamarra; Abel Montagudo Mendoza; Oliver L. Phillips; Timothy R. Baker; J. Sebastián Tello; Kenneth J. Feeley (Global Change Biology, 2026)
Forests are vital for regulating climate and sustaining biodiversity, but climate change threatens their ability to do so, especially in the tropics. Our knowledge of how tropical forests and their constituent trees will respond to changes in climate is largely based on functional trait studies; however, few previous studies have investigated trait changes within individual tropical trees across decades, limiting our ability to predict the future of these forests. In this study, we leveraged historical and contemporary botanical specimens collected from the same individual trees in the southern Peruvian Amazon, measured a suite of leaf traits to test for individual‐level trait changes over nearly 40 years, and then related these changes to concurrent changes in local climate. We hypothesized that trees have acclimated their functional traits in response to increasing air temperatures and drought intensification and that this acclimation should help to maintain stable leaf temperatures through time. In accord with our hypothesis, we found significant decreases in measured leaf traits, including size and shape metrics and stomatal traits, within individuals through time. We used these measured traits to model leaf temperatures through time, which increased faster than would be expected based on changes in air temperature alone. This accelerated warming of leaves was due to decreased stomatal conductance, a potential acclimation of trees to dry season intensification and rising [CO 2 ], thus limiting leaf transpirational cooling. In other words, trees have decreased abilities to cool their leaves, and consequently they may be approaching critical thermal thresholds faster than they would in the absence of water limitation. Our study provides evidence that while individual trees are acclimating to climate change, tropical forests are undergoing increasing thermal stress and that intensifying drought may be elevating this risk.

Insights from three decades of IUCN Red List assessments catalyzing shark, ray, and chimaera conservation - Brittany Finucci; Cassandra L. Rigby; Nicholas K. Dulvy; Rachel D. Cavanagh; Sarah Fowler; Lucy R. Harrison; Julia M. Lawson; Riley Pollom; Colin A. Simpfendorfer; Rachel H. L. Walls; Rima W. Jabado (Conservation Biology, 2026)
The International Union for Conservation of Nature (IUCN) Red List of Threatened Species is a critical measure of global aquatic and terrestrial biodiversity status. It is also the basis for the Red List Index, which tracks extinction risk over time. Sharks, rays, and chimaeras (Chondrichthyes) have now been comprehensively assessed twice (1996–2011 and 2012–2021) with hindcast assessments from 1970 onward, yielding an unprecedented extinction risk trajectory for an aquatic vertebrate class. The three‐decade success of the IUCN Species Survival Commission (SSC) Shark Specialist Group (SSG) in providing updated and evidence‐based assessments stems from sustained and coordinated activities by SSG members. We examined how a community of dedicated experts organized to fill gaps in key information to inform Red List assessments. From this evaluation, we identified six key lessons related to membership, taxonomic changes, implementation of the precautionary approach, information prioritization, assessment standardization, and policy efforts. However, existing challenges, including resource constraints and assessment discrepancies at different spatial scales, need to be addressed to ensure Red List assessments stay on pace with advances in conservation. With the second global assessment of chondrichthyans completed, it is appropriate to reflect on the evolution of the SSG and its achievements over three decades to highlight new tools and approaches to red listing and to identify priorities for the immediate future that are also applicable to other aquatic taxa with limited data, slow life histories, and exposure to high levels of fishing.

Building climate resilient urban forests: Impacts of irrigation and heat on tree establishment in a legacy city - Erika R. Wright; Christopher B. Riley; Ellen Danford; Samuel F. Ward; Mary M. Gardiner (Urban Forestry & Urban Greening, 2026)

Ecosystem engineering by primary consumers increases long-term benthic primary production in Lake Mývatn, Iceland - Anthony R. Ives; Amanda R. McCormick; Joseph S. Phillips; K. Riley Book; Emily L. Adler; Jamieson C. Botsch; Árni Einarsson (Aquatic Ecology, 2026)
Ecosystem engineers impact ecosystems by changing the physical environment in which species interact. In Lake Mývatn, Iceland, larvae of the midge Tanytarsus gracilentus function as ecosystem engineers by building tubes in the sediment that solidify the benthic surface and create a 3-dimensional structure on which microalgae can grow. To assess the ecosystem-scale effect of midge engineering, we took advantage of the natural high-amplitude fluctuations in T. gracilentus over a 13-year time series. We combined larval abundance data with benthic primary production under saturating light conditions (P max ) and pelagic in situ gross primary production (GPP) measured on average 8.4 times per summer. T. gracilentus abundance had a positive effect on benthic P max , as expected from their ecosystem engineering, while pelagic GPP had a negative effect on benthic P max , reflecting competition from phytoplankton. A complementary analysis of five replicate sediment cores taken on each of 26 sampling days of the time series shows a quantitatively similar positive effect of local-scale variation in larval midge abundance on benthic net ecosystem production (NEP) in space. Finally, we reanalyzed data from an experiment manipulating light levels and the presence/absence of midge larvae to show that larval engineering increased benthic NEP more at low than at high light levels. This indicates that at least part of the positive engineering effect of midges on benthic P max arises from amelioration of light limitation through self-shading, likely due to the structure created by midge tubes. These results show that Mývatn's high benthic primary productivity is due not only to high inputs of nutrients but also to the ecosystem engineering of tube-forming midges.

The distribution and photobiont characteristics of two lichen species along a resource gradient from the shoreline of Lake Mývatn, Iceland - Guillermo J. Ortiz; Jamieson C. Botsch; K. Riley Book; Anthony R. Ives (Aquatic Ecology, 2026)
Organisms that move across ecosystem boundaries can create resource gradients in adjacent ecosystems. Midges that emerge from Lake Mývatn, Iceland, are deposited as nutrient-rich carcasses on land, and this generates a nutrient gradient from its shoreline. We contrasted the distribution and photobiont characteristics of two lichen species, Nephromopsis cucullata and Peltigera leucophlebia, in a lava field adjacent to Mývatn along this midge deposition gradient. While the primary photobionts of P . leucophlebia and N . cucullata are green algae, P . leucophlebia also contain nitrogen-fixing cyanobacteria. Because the landscape surrounding Mývatn is generally nitrogen-limited and midge carcasses are nitrogen-rich, we hypothesized that the different photobiont associations would result in contrasting distributions between species and contrasting photobiont characteristics within species along the midge gradient. We found that N . cucullata was at its highest density 100 m from the lakeshore, while P . leucophlebia was more evenly distributed. Both species had a larger photobiont layer thickness near the lakeshore, although N . cucullata had a negative relationship between chlorophyll-a concentration (as measured using a greenness index) and distance, whereas P . leucophlebia showed no pattern. The contrasts between N . cucullata and P . leucophlebia may be related to the presence of cyanobacteria in P . leucophlebia , which provide nitrogen and, in part, decouple P . leucophlebia from the midge nitrogen deposition gradient. This study illustrates that nutrient gradients may alter lichen distributions and photobiont characteristics and suggests that these responses are primarily taxon-specific. Furthermore, it highlights the capacity for the dynamics of aquatic ecosystems to propagate into adjacent landscapes.

Benthic and pelagic nutrients vary over space and time in a shallow subarctic lake - Jamieson C. Botsch; K. Riley Book; Joseph S. Phillips; Anthony R. Ives (Aquatic Ecology, 2026)
Inorganic nutrients can vary over space and time in lakes due to abiotic and biotic factors. To understand the drivers of spatial variation in nutrients in shallow Lake Mývatn, Iceland, we mapped dissolved inorganic and organic nitrogen (N) and phosphorus (P) concentrations in benthic (interstitial) and pelagic zones in summer 2021 during a lake-wide pelagic cyanobacterial bloom and in spring 2022 when there was no cyanobacterial bloom. We expected the bloom to affect nutrient distributions between zones through shading and N 2 fixation. Nutrient concentrations were neither correlated between the benthic and pelagic zone nor correlated between sampling events. The low ratio of total dissolved N to P implied that the benthos was N-limited, while the pelagic zone switched from N to P limitation during the summer cyanobacterial bloom. Interstitial ammonium concentrations were higher in summer than spring sampling events, positively associated with depth, and negatively associated with epipelic diatom density, associations that were stronger in spring. In summer, pelagic phosphate was highest near the springs; this pattern was reversed in the spring sampling event, although the effect size was weak. Variation in interstitial phosphate was not strongly associated with any of our predictors. Pelagic ammonium, and both interstitial and pelagic nitrate, were near or below detection limits. Together, these results highlight the capacity for large spatiotemporal variation in dissolved inorganic and organic N and P concentrations and nutrient limitation which will impact the structure and function of the Mývatn ecosystem.

Dynamics and drivers of benthic crustaceans in Lake Mývatn - Emily L. Adler; Adriana Kirk; Árni Einarsson; Elijah M. Burns; Ian S. Hart; K. Riley Book; Anthony R. Ives (Aquatic Ecology, 2026)
The community of benthic crustaceans in Lake Mývatn, Iceland, is dynamic, with different taxa showing different patterns of variation through time. Here, we analyze the dynamics of eight crustaceans collected during the summer from a central station in Mývatn over 29 years, 1995–2023. We investigated the hypothesis that fluctuations in the dominant benthic tube-forming midge, Tanytarsus gracilentus , drives fluctuations in benthic crustacean abundance. We also investigated two additional drivers: predatory three-spined stickleback ( Gasterosteus islandicus ) and water clarity as a measure of pelagic phytoplankton density. The analyses identified three groups of crustaceans whose populations are correlated with other members of the same group and which show similar responses to the drivers. The group of infaunal taxa fluctuated asynchronously with T. gracilentus , with the crustaceans reaching high abundances when T. gracilentus had low abundance. The bentho-pelagic taxa and Eurycercus lamellatus (treated as a group by itself) were not strongly influenced by T. gracilentus. These patterns derived from time-series data were supported by spatial data collected from a transect along a gradient of T. gracilentus abundance in 2024; those taxa that were present in the spatial transect showed similar responses to midge abundance. While stickleback and water clarity did have an impact on some taxa, this study largely confirms that T. gracilentus is the major driving force behind changes in the benthic crustacean community dynamics. The different responses of taxa to drivers and their asynchronous fluctuations increase the stability of the benthic crustacean community by ensuring that, in any given year, some taxa are relatively abundant.

Patterns of benthic and pelagic nitrogen fixation and retention in Lake Mývatn - K. Riley Book; Jamieson C. Botsch; Ian S. Hart; Árni Einarsson; Anthony R. Ives (Aquatic Ecology, 2026)
In nitrogen-limited lakes, cyanobacterial nitrogen (N) fixation rates can be high. However, the effect of cyanobacterial N fixation on ecosystem N availability depends, in part, on the retention of fixed N. Here, we explore patterns of benthic and pelagic N fixation and fixed N retention in Lake Mývatn, Iceland. Our N budget, updated from previous assessments, showed that the annual rate of lake-scale N fixation needed to account for the deficit between external N supply and N loss varies greatly from year to year, primarily due to variation in the magnitude of N loss via outflow and midge emergences that transport and deposit N on the shore. Extrapolations from recent direct measurements of pelagic and benthic N fixation under scenarios of different benthic and pelagic N-fixer abundances showed that the capacity for N fixation is much higher in the pelagic than the benthic zone. We then explored the degree to which N fixed in the pelagic zone is retained and recycled within the lake using a dynamic N budget that leverages data on patterns of N loss via the outlet river Laxá. This revealed that approximately two-thirds of organic N in the pelagic zone must be incorporated into the benthos to explain patterns of N loss via outflow from the river Laxá. Together, these results suggest N fixation in pelagic cyanobacterial blooms may supply most of the N for benthic primary production in Mývatn.

Balancing risk and reward: Toward resilient human–primate coexistence in a rapidly changing environment in Sulawesi, Indonesia - Amanda L. Ellwanger; Kristen S. Morrow; Ashni Kumar Dhawale; Henry R. Scharf; Putu Oka Ngakan; Erin P. Riley (Ambio, 2026)
This study explores human–moor macaque ( Macaca maura ) coexistence in Sulawesi, Indonesia, using resilience thinking to assess temporal patterns of coadaptation amidst stressors such as provisioning and road construction. Comparing data from 2016–2017 to 2023–2025, we examine changes in provisioning patterns, macaque roadside use, and people’s perceptions of macaques to evaluate factors that may test the system’s resilience. Our results show that although provisioning frequency has remained stable, hand-feeding is increasingly common and macaques have increased their use of roadside habitat. Additionally, people’s perceptions have shifted from excitement and novelty to fear and normalization. Decreasing tolerance, coupled with increased risks associated with roadside behavior, highlights the system’s potential to transition to a state incompatible with coexistence. Our results can be leveraged to promote resilient coexistence, e.g., interventions that enable safer roadside crossing for the macaques and community outreach programs that make use of people’s empathy for the macaques’ welfare.

Fine‐Scale Ecological Biomonitoring in a Large, Complex Agriculturally Impacted Watershed via eDNA Metabarcoding - Bráulio S. M. L. Silva; Andrew C. Riley; Emilia Craiovan; Michael Wright; Katherine Watson; David R. Lapen; Mehrdad Hajibabaei (Molecular Ecology, 2026)
DNA‐based approaches utilizing high‐throughput sequencing (HTS) (e.g., DNA metabarcoding) have revolutionized ecological biomonitoring by providing higher sample throughput, greater reproducibility, and better cost‐benefits compared to traditional morphology‐based bioassessment studies. Here, we utilized DNA metabarcoding in a watershed in Ontario (Canada) dominated by agricultural land uses. Our aim is to understand patterns of biodiversity in benthic taxa from data generated and inferred at various taxonomic scales and to compare these findings with over a decade of traditional morphological data. We sampled 18 watercourses during summer and fall 2023, spanning a forested‐to‐agricultural land‐use gradient. We found significant differences between metabarcoding and historical morphology data where DNA provided more richness values at both the species ( p = 2 × 10 −5 ) and order ( p = 0.008) levels. Whereas the morphology dataset contained many unresolved taxa, DNA metabarcoding captured a broader taxonomic breadth with diverse genetic profiles among taxa. Non‐metric multidimensional scaling (NMDS) analyses on DNA metabarcoding data produced tighter clusters, more precise separation by land use, and greater consistency across taxonomic scales. Both urban context and land use had significant associations with metabarcoding patterns observed, with differences being strongest between agriculturally‐dominated and primarily forested sites (median R 2 ≈0.08–0.11). We also found strong, consistent environmental signals linked to agricultural settings, such as water conductivity, turbidity, and pH. Altogether, our DNA‐based results demonstrate the differences in community composition among different land uses in this watershed. Importantly, our work highlights the need for more taxonomic resolution (obtained through DNA analysis) to decipher community changes linked to anthropogenic and environmental drivers, as morphological data alone may lack the precision needed to capture these patterns.

EveryOne, EveryWhere, EveryWhen: Just water futures for three Living Rivers - R. Quentin Grafton; Anne Poelina; William Brian (Badger) Bates; Matthew Currell; David Doyle; Kirsty Howey; Cecilia Lake; Caroline McFarlane; Anthony McLarty; Nhat-Mai Nguyen; Sam Phelan; Patricia Riley; et al. (Water Security, 2026)

Geochemical characterisation of the Ellsworth-Whitmore Mountains crustal block: a critical piece in the puzzle to unravel ice retreat in West Antarctica - Emily J. Archibald; James W. Marschalek; Adrian R. Muxworthy; Teal R. Riley; Claus-Dieter Hillenbrand; Tom A. Jordan; Pieter Vermeesch; Michael J. Flowerdew; Martin Siegert; Dominic A. Hodgson; Tina van de Flierdt (Chemical Geology, 2026)

Three pairs of fungal Trametes strains isolated from distinct geographic origins show conserved genomic features and adaptive response to plant biomass - E. Drula; D. Navarro; J. Lambert; D. Chaduli; A. Lomascolo; C. Heilmann; S. Grisel; K. Barry; K. Labutti; B. Andreopoulos; L. Siyoun; S. Tejomurthula; et al. (Bioresource Technology, 2026)

A Review of Advances in Nutrition Research towards Commercial Aquaculture of Pompanos, Trachinotus spp. - Nicholas Romano; Juan F. Paredes; Fernando Yamamoto; Paul S. Wills; Charles R. Weirich; Kenneth L. Riley (Reviews in Aquaculture, 2026)
Among the jack family (Carangidae), pompanos, Trachinotus spp., are the most farmed globally. The top four most aquacultured species are golden pompano, T. ovatus , snubnose pompano, T. blochii , Indian pompano, T. mookalee , and Florida pompano, T. carolinus . While initial efforts to culture these species heavily relied on wild‐caught small fish of various species (commonly referred to as ‘trash fish’) for growout, pompanos can readily accept and thrive on formulated pelleted feeds. This has largely been accomplished through decades of nutritional research where marine‐based ingredients can be feasibly replaced with plant and animal‐based protein mixtures as long as essential amino acids, including taurine, and long‐chain polyunsaturated fatty acids meet their nutritional requirements. Obstacles still exist, including relatively poor feed efficiency, despite having a high digestibility of various ingredients, along with major research gaps in pompano nutrition and feed management of late juveniles to near‐market sized adults. Additionally, nutritional research on vitamin requirements as well as “functional feeds” and “finishing diets” designed for pompano is also relatively limited. After briefly describing the research history and production of the four most commonly farmed Trachinotus species, the main focus will be on discussing the feasibility of using alternatives to marine‐based ingredients, the influence of different starch sources, vitamin/mineral requirements, the success of “functional feeds” and the effectiveness of different feed management strategies in pompano aquaculture.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

A review of the cast stone formulation for nuclear waste immobilization - R. Matthew Asmussen; Gemma G. Clark; Jacob Anderson; Agathe Bourchy; Jacqueline Ferrer; Christopher Hossack; Jonathan Lapeyre; Miroslava Peterson; Suraj A. Rahmon; Joelle T. Reiser; Brian J. Riley; Sarah A. Saslow; et al. (Waste Management, 2026)

Age of granitoid magmatism in South Georgia and correlations to southern Patagonia and the northern Antarctic Peninsula - Teal R. Riley; Andrew Carter (Journal of South American Earth Sciences, 2026)

Domestication During Restoration: Unintentional Selection During Eight Generations of Wild Seed Propagation Reduces Herkogamy, Dichogamy and Heterozygosity in Clarkia pulchella - Julie R. Etterson; Paige Fliehr; Riley Pizza; Briana L. Gross (Molecular Ecology, 2025)
Seed production on native seed farms has increased to meet the rising demand for plant material for restoration. Although these propagation efforts are necessary for restoration, cultivating wild populations may also result in unintentional selection and elicit evolutionary changes that mimic crop domestication, essentially turning these efforts into artificial domestication experiments. Here, we investigated whether phenotypic and genomic changes associated with domestication occurred in the wildflower Clarkia pulchella Pursh (Onagraceae) by comparing the wild source populations to the farmed population after eight generations of cultivation. At the phenotypic level, the farmed population shifted towards a floral morphology associated with self‐pollination, with a significant decrease in both dichogamy and herkogamy. At the genomic level, > 6500 SNPs revealed that mean expected heterozygosity of the farmed population was significantly lower than the wild populations, despite the fact that the farmed population originated from a pool of multiple wild populations. Both the shift towards a selfing phenotype and the loss of diversity are expected consequences of domestication, although the phenotypic shifts in particular occurred much more rapidly than has been observed for other domestication traits. We discuss these results in the context of plant domestication and the implications for retaining the genetic integrity of wild populations during the process of seed production for restoration.

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

Age and geology of granitoids in northeast Palmer Land, Antarctic Peninsula - Ryan North; Lloyd T. White; Teal R. Riley; Dominique Tanner; Timothy T. Barrows (Lithos, 2025)

Foraminifera record historical coral-algal phase shifts on Caribbean coral reefs - Akos Kalman; Alex F. Humphreys; Zach Adams; Riley Ames; Angelique R. Marín; Alex C. Dempsey; Sam J. Purkis (Marine Environmental Research, 2025)

Significant mortality of old trees across a dry forest landscape, Oregon, USA - James D. Johnston; Paige N. Stephens; Micah R. Schmidt; Sean M.A. Jeronimo; Amanda E. Brackett; Amarina E. Wuenschel; Danielle E.M. Ulrich; Riley H. Paine; Lou F. Duloisy; Skye M. Greenler; Andrew J. Larson; Derek J. Churchill (Forest Ecology and Management, 2025)

Alternative approaches to lead sampling in drinking water: A comparative study of homes with and without lead service lines in two cities - Darren A. Lytle; Megan Urbanic; Alexander Paul; Riley Achtemeier; Alan T. Lewis; Shannon N. Hammaker; Anjelica P. Estep; Mallikarjuna N. Nadagouda; Ryan R. James; Simoni Triantafyllidou (Science of The Total Environment, 2025)

Ventilatory and perceptual habituation achieved with twice-daily, six total brief 12 °C head-out water immersions - Afton D. Seeley; Thomas A. Mayer; Shaun C. Brazelton; David H. Gonzalez Rojas; Kathryn G. McCarthy; Phillip O. Bodurtha; Molly E. Heikkinen; Gabrielle E.W. Giersch; MariaLena A. Shaw; Andrew M. Greenfield; Karleigh E. Bradbury; Koby C. Conz; et al. (Journal of Thermal Biology, 2025)

Genetic variation and synonymous cultivars in the USDA lychee (Litchi chinensis Sonn.) collection assessed using genome-wide SNPs - Joseph Rootkin; Grace Harrison-Tate; Carol R. Mayo-Riley; Tracie Matsumoto; Mark A. Chapman (Genetic Resources and Crop Evolution, 2025)
Lychee ( Litchi chinensis ) fruits have high nutritional and pharmacological value, yet the crop is underutilized on global markets partly due to cultivation problems outside the native area and lack of knowledge/misidentification of cultivars. Using reduced representation sequencing, 78 trees representing 57 cultivars plus 13 trees without varietal names from the USDA lychee collection on Hawai’i were analysed. We aimed to (1) understand the distribution of genetic variation, (2) ensure individuals of the same named variety were indeed likely the same cultivar, and (3) to identify cases of cultivar synonymy. After removing single nucleotide polymorphisms (SNPs) with substantial missing data, rare alleles and low confidence SNPs, analysis of ca. 10,400 SNPs was carried out. Genetic clustering and phylogenetic analysis identified two main groups which, based on existing data, represent the late and extremely early maturing cultivars, with many admixed individuals likely representing those with intermediate maturity times. A core set of 12 SNPs for cultivar identification were identified. Trees from the same named variety were not always closely related, representing misidentification. Similarly, some trees with different varietal names appear to be the same (i.e., synonymous cultivars); in some cases, this backed up existing knowledge about the transport and renaming of cultivars between countries. Based on genetic similarity, we found 13 groups of clones varying in size from 2–9 individuals. Fifty-five of the 91 trees (60%) were in these groups. Together, our data has the potential to inform the conservation of lychee accessions and backs up previous work that there are primarily two domesticated gene pools with a third group of accessions being admixed. Going forward, our results could lead to the improvement of lychee, a step in making it a staple crop.

Metabolic modelling of anaerobic amino acid uptake and storage by fermentative polyphosphate accumulating organisms - R. Thomson; K. Close; A. Riley; D.J. Batstone; A. Oehmen (Water Research, 2025)

Alkaloid induction by the interaction between Annona purpurea Moc. & Sessé ex Dunal Curvularia lunata (Wakker) Boedijn and Rhizopus stolonifer Ehrenb. (Ex Fr.) Lind. - K.A. Toledo-González; C.A. Riley-Saldaña; R. Salas-Lizana; I. De-la-Cruz-Chacón; A.R. González-Esquinca (Phytochemistry Letters, 2025)

TropiRoot 1.0: Database of tropical root characteristics across environments - Amanda L. Cordeiro; Daniela F. Cusack; Nathaly Guerrero‐Ramírez; Richard J. Norby; Laura Toro; Michelle Y. Wong; S. Joseph Wright; Kristine Grace M. Cabugao; Kelly M. Andersen; Lucia Fuchslueger; Colleen M. Iversen; Fiona Soper; et al. (Ecology, 2025)
Tropical ecosystems contain the world's largest biodiversity of vascular plants. Yet, our understanding of tropical functional diversity and its contribution to global diversity patterns is constrained by data availability. This discrepancy underscores an urgent need to bridge data gaps by incorporating comprehensive tropical root data into global datasets. Here, we provide a database of tropical root characteristics. This new database, TropiRoot 1.0, will be instrumental in evaluating an array of hypotheses pertaining to root functional ecology and plant biogeography, both within the tropics and relative to other global biomes. The data compilation was conducted by the TropiRoot Initiative, in partnership with the Fine‐Root Ecology Database (FRED) and the Global Root Trait (GRooT) database, Colorado State University (CSU) and the Smithsonian Tropical Research Institute (STRI). Literature search and data extraction were conducted between 2020 and 2024. Literature was identified using Web of Science, Scopus, and complemented using the expert knowledge of members of TropiRoot. To provide broad environmental and geographical distributions, literature searches included root characteristics (traits) across global change drivers, natural gradients, and from different continents. We adopted FRED standardized data columns and streamlined the format to enhance accessibility for data extraction across various user groups. This optimized framework resulted in a smaller, yet comprehensive datasheet. To make the database compatible with other global root trait initiatives, column identification was standardized following the codes provided by FRED. These efforts culminated in data extracted from 104 new sources, resulting in more than 8000 rows of data (either species or community data). Most of the data in TropiRoot 1.0 include root characteristics such as root biomass, morphology, root dynamics, mass fraction, architecture, anatomy, physiology, and root chemistry. This initiative represents a 30% increase in the currently available data for tropical roots in FRED. TropiRoot 1.0 contains root characteristics from 25 different countries, where seven are located in Asia, six in South America, five in Central America and the Caribbean, four in Africa, two in North America, and 1 in Oceania. Due to the volume of data, when ancillary data were available, including soil data, these data were either extracted and included in the database or its availability was recorded in an additional column. Multiple contributors checked the entries for outliers during the collation process to ensure data quality. For text‐based observations, we examined all cells to ensure that their content relates to their specific categories. For numerical observations, we ordered each numerical value from least to greatest and plotted the values, checking apparent outliers against the data in their respective sources and correcting or removing incorrect or impossible values. Some data (soil and aboveground) have different columns for the same variable presented in different units, including originally published units, but root characteristics data had units converted to match those reported in FRED. By filling a gap from global databases, TropiRoot 1.0 expands our knowledge of otherwise so far underrepresented regions and our ability to assess global trends. This advancement can be used to improve tropical forest representation in vegetation models. The data are freely available and should be cited when used.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Local-scale hydrogeologic controls on groundwater discharge to a ferruginous meromictic kettle lake - Riley Kniptash; Sajjad A. Akam; Elizabeth D. Swanner; Jessica R. Meyer (Hydrogeology Journal, 2025)

Laboratory‐Reared Lobster Larvae Yield Inaccurate Estimates of Thermal Tolerance - Eric R. Annis; Aubrey Jane; Markus Frederich; Jesica Waller; Claire D. Fecteau‐Volk; Hannah O'Loughlin; Riley Larkin; Douglas B. Rasher (Global Change Biology, 2025)
Physiological response to temperature stress defines the distribution of many marine invertebrates, and their thermal limits provide a foundation for understanding marine invertebrate response to climate change. In bottom dwelling species with free swimming planktonic larvae, such as the American lobster ( Homarus americanus ), thermal tolerance of early life stages influences vertical distribution in the water, settlement patterns on the bottom, and ultimately the species' range. We used measures of scope for activity, size, survivorship, and molecular techniques to demonstrate that wild‐caught lobster larvae were more tolerant of temperature stress than laboratory‐reared larvae (reared at 18°C and fed brine shrimp). Thermal tolerance in wild larvae exceeded both upper and lower critical temperatures of laboratory‐reared larvae by approximately 5°C. The difference appeared to be driven by diet and acclimation temperature, yet altering these parameters still did not produce larvae with a range of thermal tolerance equal to wild larvae. We report that nearly all studies examining physiological response to temperature in marine invertebrate larvae have used laboratory‐reared larvae and no studies have compared their thermal tolerance to wild larvae. The lack of similar comparisons in other species reveals a significant gap in our understanding of organismal response to temperature stress spanning multiple phyla. Our research is a novel effort to close this gap and better represent how this species responds to global climate change driven extremes.

Glacial geology of the Hudson Mountains, Amundsen Sea sector, West Antarctica - Joanne S. Johnson; Keir A. Nichols; Teal R. Riley; Ryan A. Venturelli; Dominic A. Hodgson; Greg Balco; Brenda Hall; James A. Smith; John Woodward (Quaternary Science Reviews, 2025)

Do the biological characteristics of trout ( Salmo trutta ) smolts influence their spring migration timing and maiden marine sojourn duration? - Jonathan P. Gillson; Robert E. Blackwell; Stephen D. Gregory; Jessica E. Marsh; Tea Bašić; Sophie A. M. Elliott; R. Andrew King; David L. Maxwell; William D. Riley; Jamie R. Stevens; Alan M. Walker; Rasmus B. Lauridsen (Journal of Fish Biology, 2025)
Anadromous salmonids migrate seaward to exploit feeding and growth opportunities in marine habitats, yet how smolt biological characteristics influence their marine migratory behavior remains poorly understood. This study used 9 years of trout ( Salmo trutta ) population monitoring data from 15,595 tagged age‐0+ parr, 1033 smolts detected migrating downstream in spring, and 99 adults detected returning from their first marine migration to the River Frome (Dorset, UK) to investigate the influence of smolt biological characteristics on their migration timing and maiden marine sojourn duration. Age‐specific differences in the influence of smolt length on migration timing were found, with longer 1‐year‐old smolts emigrating later than their shorter counterparts within the same age class, but the opposite association existed for 2‐year‐old smolts. A bespoke integrated statistical model quantified the effects of smolt emigration day of year, age, sex, and length on the probability of first‐time migrants returning to the river after one or more sea winters. Younger, later migrating smolts had a longer marine sojourn duration than their older, earlier migrating counterparts, and females remained at sea for longer periods than males. Although the statistical model was designed to maximize the use of information available in the data, it revealed only weak effects of smolt biological characteristics on the maiden marine sojourn duration. A complementary simulation study suggested that detecting more spring migrating smolts and analyzing longer time series of trout population monitoring data would increase the ability to detect statistically significant effects. Therefore, a strategic review of the trout population monitoring program, including more long‐term biological data collection, is recommended. The modelling work presented here can provide guidance on the size of the required dataset and how to maximize the power of imperfect data.

A Functional Response in Resource Selection Links Multiscale Responses of a Large Carnivore to Human Mortality Risk - Kyle D. Dougherty; Justin A. Dellinger; Bogdan Cristescu; Daniel J. Gammons; David K. Garcelon; J. Mark Higley; Quinton E. Martins; Seth P. D. Riley; Jeff A. Sikich; Thomas R. Stephenson; T. Winston Vickers; Greta M. Wengert; et al. (Ecology Letters, 2025)
Theory suggests that animals make hierarchical, multiscale resource selection decisions to address the hierarchy of factors limiting their fitness. Ecologists have developed tools to link population‐level resource selection across scales; yet, theoretical expectations about the relationship between coarse‐ and fine‐scale selection decisions at the individual level remain elusive despite their importance to fitness. With GPS‐telemetry data collected across California, USA, we evaluated resource selection of mountain lions ( Puma concolor ; n = 244) relative to spatial variation in human‐caused mortality risk. With hierarchical resource selection, coarse‐scale selection determines availability at finer scales. This simple relationship allowed us to demonstrate that functional responses in resource selection explicitly link individual‐level resource selection decisions across scales. We show that individuals proactively avoiding risk when selecting home ranges are freed to relax this avoidance when making decisions within home ranges. However, individuals also exhibit reactive avoidance of risk at the finest scales along movement paths.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Reinvestigating the Dufek Intrusion, through joint gravity and magnetic models - Tom A. Jordan; Teal R. Riley (Physics of the Earth and Planetary Interiors, 2024)

Connectivity of toxigenic Pseudo-nitzschia species assemblages between the Northeast U.S. continental shelf and an adjacent estuary - Katherine M. Roche; Isabella N. Church; Alexa R. Sterling; Tatiana A. Rynearson; Matthew J. Bertin; Andrew M. Kim; Riley D. Kirk; Bethany D. Jenkins (Harmful Algae, 2024)

Air pollution, genetic factors, and chronic rhinosinusitis: A prospective study in the UK Biobank - Qinfeng Zhou; Junxiong Ma; Shyam Biswal; Nicholas R. Rowan; Nyall R. London; Charles A. Riley; Stella E. Lee; Jayant M. Pinto; Omar G. Ahmed; Mintao Su; Zhisheng Liang; Runming Du; et al. (Science of The Total Environment, 2024)

City divided: Unveiling family ties and genetic structuring of coyotes in Seattle - Samantha E. S. Kreling; Ellen M. Reese; Olivia M. Cavalluzzi; Natalee B. Bozzi; Riley Messinger; Christopher J. Schell; Robert A. Long; Laura R. Prugh (Molecular Ecology, 2024)
Linear barriers pose significant challenges for wildlife gene flow, impacting species persistence, adaptation, and evolution. While numerous studies have examined the effects of linear barriers (e.g., fences and roadways) on partitioning urban and non‐urban areas, understanding their influence on gene flow within cities remains limited. Here, we investigated the impact of linear barriers on coyote ( Canis latrans ) population structure in Seattle, Washington, where major barriers (i.e., interstate highways and bodies of water) divide the city into distinct quadrants. Just under 1000 scats were collected to obtain genetic data between January 2021 and December 2022, allowing us to identify 73 individual coyotes. Notably, private allele analysis underscored limited interbreeding among quadrants. When comparing one quadrant to each other, there were up to 16 private alleles within a single quadrant, representing nearly 22% of the population allelic diversity. Our analysis revealed weak isolation by distance, and despite being a highly mobile species, genetic structuring was apparent between quadrants even with extremely short geographic distance between individual coyotes, implying that Interstate 5 and the Ship Canal act as major barriers. This study uses coyotes as a model species for understanding urban gene flow and its consequences in cities, a crucial component for bolstering conservation of rarer species and developing wildlife friendly cities.

To house or oust: Honey bee (Apis mellifera) colonies can evaluate and evict drones of low quality - Izaak R. Gilchrist; Jonathan M. Nixon; Riley R. Shultz; Matthew D. Ginzel; Brock A. Harpur (Behavioral Ecology and Sociobiology, 2024)
Across the animal kingdom, males advertise their quality to potential mates. Males of low reproductive quality, such as those that are sick, may be excluded from mating. In eusocial species, there is some evidence that reproductive females gauge the quality of their mates. However, males often spend much more time with non-reproductive females when being raised or when returning from unsuccessful mating flights. Do non-reproductive workers evaluate the quality of male reproductives? Here we address this question using male honey bees ( Apis mellifera ), called drones, as a model. We generated immune-challenged drones by injecting them with lipopolysaccharide and tested: 1) do workers evict immune-challenged drones from their colony, 2) do cuticular hydrocarbon (CHC) profiles, body size, or mass change when drones are immune-challenged, and 3) are these changes used by workers to exclude low quality males from the colony? We found that an immune challenge causes changes in CHC profiles of drones and reduces their body mass. Workers selectively evict small and immune-challenged drones who, themselves, do not self-evict. This work demonstrates that some eusocial males undergo an additional layer of scrutiny prior to mating mediated by the non-reproductive worker caste. Significance statement Males of some species must advertise their quality to mates but, in the case of eusocial species, must they also advertise their quality to nestmates? By manipulating honey bee male quality, we found that small and immune-challenged drones are evicted from colonies overnight. Workers may not use a drone’s cuticular hydrocarbon profile to make this assessment. This is a new example of social immunity expressed against adult males and an example of worker involvement in reproductive decisions.

Disentangling the drivers of decadal body size decline in an insect population - Jamieson C. Botsch; Aayush N. Zaveri; Lucas A. Nell; Amanda R. McCormick; K. Riley Book; Joseph S. Phillips; Árni Einarsson; Anthony R. Ives (Global Change Biology, 2024)
While climate warming is widely predicted to reduce body size of ectotherms, evidence for this trend is mixed. Body size depends not only on temperature but also on other factors, such as food quality and intraspecific competition. Because temperature trends or other long‐term environmental factors may affect population size and food sources, attributing trends in average body size to temperature requires the separation of potentially confounding effects. We evaluated trends in the body size of the midge Tanytarsus gracilentus and potential drivers (water temperature, population size, and food quality) between 1977 and 2015 at Lake Mývatn, Iceland. Although temperatures increased at Mývatn over this period, there was only a slight (non‐significant) decrease in midge adult body size, contrary to theoretical expectations. Using a state‐space model including multiple predictors, body size was negatively associated with both water temperature and midge population abundance, and it was positively associated with 13 C enrichment of midges (an indicator of favorable food conditions). The magnitude of these effects were similar, such that simultaneous changes in temperature, abundance, and carbon stable isotopic signature could counteract each other in the long‐term body size trend. Our results illustrate how multiple factors, all of which could be influenced by global change, interact to affect average ectotherm body size.

Diversity–stability relationships across organism groups and ecosystem types become decoupled across spatial scales - Nathan I. Wisnoski; Riley Andrade; Max C. N. Castorani; Christopher P. Catano; Aldo Compagnoni; Thomas Lamy; Nina K. Lany; Luca Marazzi; Sydne Record; Annie C. Smith; Christopher M. Swan; Jonathan D. Tonkin; et al. (Ecology, 2023)
The relationship between biodiversity and stability, or its inverse, temporal variability, is multidimensional and complex. Temporal variability in aggregate properties, like total biomass or abundance, is typically lower in communities with higher species diversity (i.e., the diversity–stability relationship [DSR]). At broader spatial extents, regional‐scale aggregate variability is also lower with higher regional diversity (in plant systems) and with lower spatial synchrony. However, focusing exclusively on aggregate properties of communities may overlook potentially destabilizing compositional shifts. It is not yet clear how diversity is related to different components of variability across spatial scales, nor whether regional DSRs emerge across a broad range of organisms and ecosystem types. To test these questions, we compiled a large collection of long‐term metacommunity data spanning a wide range of taxonomic groups (e.g., birds, fish, plants, invertebrates) and ecosystem types (e.g., deserts, forests, oceans). We applied a newly developed quantitative framework for jointly analyzing aggregate and compositional variability across scales. We quantified DSRs for composition and aggregate variability in local communities and metacommunities. At the local scale, more diverse communities were less variable, but this effect was stronger for aggregate than compositional properties. We found no stabilizing effect of γ‐diversity on metacommunity variability, but β‐diversity played a strong role in reducing compositional spatial synchrony, which reduced regional variability. Spatial synchrony differed among taxa, suggesting differences in stabilization by spatial processes. However, metacommunity variability was more strongly driven by local variability than by spatial synchrony. Across a broader range of taxa, our results suggest that high γ‐diversity does not consistently stabilize aggregate properties at regional scales without sufficient spatial β‐diversity to reduce spatial synchrony.

Observational constraints reduce model spread but not uncertainty in global wetland methane emission estimates - Kuang‐Yu Chang; William J. Riley; Nathan Collier; Gavin McNicol; Etienne Fluet‐Chouinard; Sara H. Knox; Kyle B. Delwiche; Robert B. Jackson; Benjamin Poulter; Marielle Saunois; Naveen Chandra; Nicola Gedney; et al. (Global Change Biology, 2023)
The recent rise in atmospheric methane (CH 4 ) concentrations accelerates climate change and offsets mitigation efforts. Although wetlands are the largest natural CH 4 source, estimates of global wetland CH 4 emissions vary widely among approaches taken by bottom‐up (BU) process‐based biogeochemical models and top‐down (TD) atmospheric inversion methods. Here, we integrate in situ measurements, multi‐model ensembles, and a machine learning upscaling product into the International Land Model Benchmarking system to examine the relationship between wetland CH 4 emission estimates and model performance. We find that using better‐performing models identified by observational constraints reduces the spread of wetland CH 4 emission estimates by 62% and 39% for BU‐ and TD‐based approaches, respectively. However, global BU and TD CH 4 emission estimate discrepancies increased by about 15% (from 31 to 36 TgCH 4 year −1 ) when the top 20% models were used, although we consider this result moderately uncertain given the unevenly distributed global observations. Our analyses demonstrate that model performance ranking is subject to benchmark selection due to large inter‐site variability, highlighting the importance of expanding coverage of benchmark sites to diverse environmental conditions. We encourage future development of wetland CH 4 models to move beyond static benchmarking and focus on evaluating site‐specific and ecosystem‐specific variabilities inferred from observations.

Genomic epidemiology and transmission dynamics of recurrent Clostridioides difficile infection in Western Australia - Daniel R. Knight; Korakrit Imwattana; Deirdre A. Collins; Su-Chen Lim; Stacey Hong; Papanin Putsathit; Thomas V. Riley (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
Recurrent cases of Clostridioides difficile infection (rCDI) remain one of the most common and serious challenges faced in the management of CDI. The accurate distinction between a relapse (caused by infection with the same strain) and reinfection (caused by a new strain) has implications for infection control and prevention, and patient therapy. Here, we used whole-genome sequencing to investigate the epidemiology of 94 C. difficile isolates from 38 patients with rCDI in Western Australia. The C. difficile strain population comprised 13 sequence types (STs) led by ST2 (PCR ribotype (RT) 014, 36.2%), ST8 (RT002, 19.1%) and ST34 (RT056, 11.7%). Among 38 patients, core genome SNP (cgSNP) typing found 27 strains (71%) from initial and recurring cases differed by ≤ 2 cgSNPs, suggesting a likely relapse of infection with the initial strain, while eight strains differed by ≥ 3 cgSNPs, suggesting reinfection. Almost half of patients with CDI relapse confirmed by WGS suffered episodes that occurred outside the widely used 8-week cut-off for defining rCDI. Several putative strain transmission events between epidemiologically unrelated patients were identified. Isolates of STs 2 and 34 from rCDI cases and environmental sources shared a recent evolutionary history, suggesting a possible common community reservoir. For some rCDI episodes caused by STs 2 and 231, within-host strain diversity was observed, characterised by loss/gain of moxifloxacin resistance. Genomics improves discrimination of relapse from reinfection and identifies putative strain transmission events among patients with rCDI. Current definitions of relapse and reinfection based on the timing of recurrence need to be reconsidered.

Alkaloidal variation in seedlings of Annona purpurea Moc. & Sessé ex Dunal infected with Colletotrichum gloeosporioides (Penz.) Penz. and Sacc. - K.A. Toledo-González; C.A. Riley-Saldaña; R. Salas-Lizana; I. De-la-Cruz-Chacón; A.R. González-Esquinca (Biochemical Systematics and Ecology, 2023)

Modeled production, oxidation, and transport processes of wetland methane emissions in temperate, boreal, and Arctic regions - Masahito Ueyama; Sara H. Knox; Kyle B. Delwiche; Sheel Bansal; William J. Riley; Dennis Baldocchi; Takashi Hirano; Gavin McNicol; Karina Schafer; Lisamarie Windham‐Myers; Benjamin Poulter; Robert B. Jackson; et al. (Global Change Biology, 2023)
Wetlands are the largest natural source of methane (CH 4 ) to the atmosphere. The eddy covariance method provides robust measurements of net ecosystem exchange of CH 4 , but interpreting its spatiotemporal variations is challenging due to the co‐occurrence of CH 4 production, oxidation, and transport dynamics. Here, we estimate these three processes using a data‐model fusion approach across 25 wetlands in temperate, boreal, and Arctic regions. Our data‐constrained model—iPEACE—reasonably reproduced CH 4 emissions at 19 of the 25 sites with normalized root mean square error of 0.59, correlation coefficient of 0.82, and normalized standard deviation of 0.87. Among the three processes, CH 4 production appeared to be the most important process, followed by oxidation in explaining inter‐site variations in CH 4 emissions. Based on a sensitivity analysis, CH 4 emissions were generally more sensitive to decreased water table than to increased gross primary productivity or soil temperature. For periods with leaf area index (LAI) of ≥20% of its annual peak, plant‐mediated transport appeared to be the major pathway for CH 4 transport. Contributions from ebullition and diffusion were relatively high during low LAI ( 4 production and CH 4 emissions tended to be short in fen sites (3 ± 2 days) and long in bog sites (13 ± 10 days). Based on a principal component analysis, we found that parameters for CH 4 production, plant‐mediated transport, and diffusion through water explained 77% of the variance in the parameters across the 19 sites, highlighting the importance of these parameters for predicting wetland CH 4 emissions across biomes. These processes and associated parameters for CH 4 emissions among and within the wetlands provide useful insights for interpreting observed net CH 4 fluxes, estimating sensitivities to biophysical variables, and modeling global CH 4 fluxes.

Compact capillary high performance liquid chromatography system for pharmaceutical on-line reaction monitoring - Lewellwyn J. Coates; Andrew Gooley; Shing Chung Lam; Boyjie Firme; Paul R. Haddad; Hans-Jürgen Wirth; Angel Diaz; Frank Riley; Brett Paull (Analytica Chimica Acta, 2023)

Palaeozoic – Early Mesozoic geological history of the Antarctic Peninsula and correlations with Patagonia: Kinematic reconstructions of the proto-Pacific margin of Gondwana - Teal R. Riley; Alex Burton-Johnson; Michael J. Flowerdew; Fernando Poblete; Paula Castillo; Francisco Hervé; Philip T. Leat; Ian L. Millar; Joaquin Bastias; Martin J. Whitehouse (Earth-Science Reviews, 2023)

Novel polyomaviruses identified in fecal samples from four carnivore species - Simona Kraberger; Laurel E. K. Serieys; Seth P. D. Riley; Kara Schmidlin; Eric S. Newkirk; John R. Squires; Christopher B. Buck; Arvind Varsani (Archives of Virology, 2023)

Lessons for conservation from beneath the pavement - Alexis M. Mychajliw; Elizabeth R. Ellwood; Peter S. Alagona; R. Scott Anderson; Mairin A. Balisi; Eric Biber; Justin L. Brown; Jessie George; Austin J. W. Hendy; Lila Higgins; Courtney A. Hofman; Ashley Leger; et al. (Conservation Biology, 2022)

None detected: What “zero” indicates in direct counts of aquatic microorganisms in treated ballast water - Matthew R. First; Stephanie H. Robbins-Wamsley; Scott C. Riley; Jonathan F. Grant; Vanessa Molina; Timothy P. Wier (Frontiers in Marine Science, 2022)
International limits on the concentrations of living organisms in ballast water are now in force for commercial ships. Microscopy-based, “direct count” assays estimate the concentrations of organisms. These assays are used in performance tests of Ballast Water Management Systems (BWMSs), which are shipboard technologies designed to reduce living organisms in ballast water to below the discharge limits. Here, we examine the factors that affect the method detection limit (MDL) of direct count assays. The MDL depends upon the volumes sampled, concentrated (or diluted), and analyzed, so the MDL will vary as these volumes vary from analysis-to-analysis. Decreasing the MDL to detect exceedingly rare individuals (e.g., ~1 individual per m 3 or fewer) is possible, but problematic, given the challenges in analyzing dynamic communities of living organisms: increasing sample and analysis volumes to lower the MDL will likely accelerate the loss of individuals, as organisms are concentrated to several orders of magnitude above in situ concentrations and held for extended times. Results of direct count assays may be widely disseminated as an indicator of the performance of BWMSs, and when no organisms are detected, concentrations may be shown as “0 organisms per m 3 or mL” rather than “<MDL”, as appropriate. When clearly derived and reported, a numerical MDL for the direct count assay—the lowermost value distinct from “zero”—provides context to results and transparency into the sensitivity of the assay.

Emerging harmful algal blooms caused by distinct seasonal assemblages of a toxic diatom - Alexa R. Sterling; Riley D. Kirk; Matthew J. Bertin; Tatiana A. Rynearson; David G. Borkman; Marissa C. Caponi; Jessica Carney; Katherine A. Hubbard; Meagan A. King; Lucie Maranda; Emily J. McDermith; Nina R. Santos; et al. (Limnology and Oceanography, 2022)
Diatoms in the Pseudo‐nitzschia genus produce the neurotoxin domoic acid. Domoic acid bioaccumulates in shellfish, causing illness in humans and marine animals upon ingestion. In 2017, high domoic acid levels in shellfish meat closed shellfish harvest in Narragansett Bay, Rhode Island for the first and only time in history, although abundant Pseudo‐nitzschia have been observed for over 60 years . To investigate whether an environmental factor altered endemic Pseudo‐nitzschia physiology or new domoic acid‐producing strain(s) were introduced to Narragansett Bay, we conducted weekly sampling from 2017 to 2019 and compared closure samples. Plankton‐associated domoic acid was quantified by LC‐MS/MS and Pseudo‐nitzschia spp. were identified using a taxonomically improved high‐throughput rDNA sequencing approach. Comparison with environmental data revealed a detailed understanding of domoic acid dynamics and seasonal multi‐species assemblages. Plankton‐associated domoic acid was low throughout 2017–2019, but recurred in fall and early summer maxima. Fall domoic acid maxima contained known toxic species as well as a novel Pseudo‐nitzschia genotype. Summer domoic acid maxima included fewer species but also known toxin producers . Most 2017 closure samples contained the particularly concerning toxic species, P. australis , which also appeared infrequently during 2017–2019. Recurring Pseudo‐nitzschia assemblages were driven by seasonal temperature changes, and plankton‐associated domoic acid correlated with low dissolved inorganic nitrogen. Thus, the Narragansett Bay closures were likely caused by both resident assemblages that become toxic depending on nutrient status as well as the episodic introductions of toxic species from oceanographic and climatic shifts.

Extinction risk, reconstructed catches and management of chondrichthyan fishes in the Western Central Atlantic Ocean - Brendan S. Talwar; Brooke Anderson; Cristopher G. Avalos‐Castillo; María del Pilar Blanco‐Parra; Alejandra Briones; Diego Cardeñosa; John K. Carlson; Patricia Charvet; Charles F. Cotton; Zoe Crysler; Danielle H. Derrick; Michael R. Heithaus; et al. (Fish and Fisheries, 2022)
Chondrichthyan fishes are among the most threatened vertebrates on the planet because many species have slow life histories that are outpaced by intense fishing. The Western Central Atlantic Ocean, which includes the Greater Caribbean, is a hotspot of chondrichthyan biodiversity and abundance, but has been characterized by extensive shark and ray fisheries and a lack of sufficient data for effective management and conservation. To inform future research and management decisions, we analysed patterns in chondrichthyan extinction risk, reconstructed catches and management engagement in this region. We summarized the extinction risk of 180 sharks, rays and chimaeras, including 66 endemic and 14 near‐endemic species, using contemporary IUCN Red List assessments. Over one‐third (35.6%) were assessed as Vulnerable, Endangered or Critically Endangered, primarily due to overfishing. Reconstructed catches from 1950 to 2016 peaked in 1992, then declined by 40.2% thereafter. The United States, Venezuela and Mexico were responsible for most catches in the region and hosted the largest proportions of the regional distributions of threatened species, largely due to having extensive coastal habitats in their Exclusive Economic Zones. The quantity and taxonomic resolution of fisheries landings data were poor in much of the region, and national‐level regulations varied widely across jurisdictions. Deepwater fisheries represent an emerging threat, although many deepwater chondrichthyans currently have refuge beyond the depths of most fisheries. Regional collaboration as well as effective and enforceable management informed by more complete fisheries data, particularly from small‐scale fisheries, are required to protect and recover threatened species and ensure sustainable fisheries.

Impact of infectious diseases consultation among patients with infections caused by gram-negative rod bacteria: a systematic literature review and meta-analysis - Shinya Hasegawa; Satoshi Kakiuchi; Joseph Tholany; Takaaki Kobayashi; Alexandre R. Marra; Marin L. Schweizer; Riley J. Samuelson; Hiroyuki Suzuki (Infectious Diseases, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Compassionate-use pocapavir and immunoglobulin therapy for treatment of rituximab-associated enterovirus meningoencephalitis - Samantha Epstein; Riddhi Thakkar; Kathryn T. Fong; James Ng; David R. Bearden; Nischay Mishra; Kiran T. Thakur; Claire S. Riley (Journal of NeuroVirology, 2022)

Clostridioides difficile infection and One Health: an equine perspective - Natasza M.R. Hain‐Saunders; Daniel R. Knight; Mieghan Bruce; Thomas V. Riley (Environmental Microbiology, 2022)
Summary Clostridioides (Clostridium) difficile presents a significant health risk to humans and animals. The complexity of the bacterial–host interaction affecting pathogenesis and disease development creates an ongoing challenge for epidemiological studies, control strategies and prevention planning. The recent emergence of human disease caused by strains of C . difficile found in animals adds to mounting evidence that C . difficile infection (CDI) may be a zoonosis. In equine populations, C . difficile is a known cause of diarrhoea and gastrointestinal inflammation, with considerable mortality and morbidity. This has a significant impact on both the well‐being of the animal and, in the case of performance and production animals, it may have an adverse economic impact on relevant industries. While C . difficile is regularly isolated from horses, many questions remain regarding the impact of asymptomatic carriage as well as optimization of diagnosis, testing and treatment. This review provides an overview of our understanding of equine CDI while also identifying knowledge gaps and the need for a holistic One Health approach to a complicated issue.

Genetically related Clostridium difficile from water sources and human CDI cases revealed by whole‐genome sequencing - Su‐Chen Lim; Natasza M. R. Hain‐Saunders; Korakrit Imwattana; Papanin Putsathit; Deirdre A. Collins; Thomas V. Riley (Environmental Microbiology, 2022)
Summary Clostridium difficile isolates from the environment are closely related to those from humans, indicating a possible environmental transmission route for C. difficile infection (CDI). In this study, C. difficile was isolated from 47.3% (53/112) of lake/pond, 23.0% (14/61) of river, 20.0% (3/15) of estuary and 0.0% (0/89) of seawater samples. The most common toxigenic strain isolated was C. difficile PCR ribotype (RT) 014/020 (10.5%, 8/76). All water isolates were susceptible to fidaxomicin, metronidazole, rifaximin, amoxicillin/clavulanic acid, moxifloxacin and tetracycline. Resistance to vancomycin, clindamycin, erythromycin and meropenem was detected in 5.3% (4/76), 26.3% (20/76), 1.3% (1/76) and 6.6% (5/76) of isolates, respectively. High‐resolution core‐genome analysis was performed on RT 014/020 isolates of water origin and 26 clinical RT 014/020 isolates from the same year and geographical location. Notably, both human and water strains were intermixed across three sequence types (STs), 2, 13 and 49. Six closely related groups with ≤10 core‐genome single nucleotide polymorphisms were identified, five of which comprised human and water strains. Overall, 19.2% (5/26) of human strains shared a recent genomic relationship with one or more water strains. This study supports the growing hypothesis that environmental contamination by C. difficile plays a role in CDI transmission.

Coupling plant litter quantity to a novel metric for litter quality explains C storage changes in a thawing permafrost peatland - Moira Hough; Samantha McCabe; S. Rose Vining; Emily Pickering Pedersen; Rachel M. Wilson; Ryan Lawrence; Kuang‐Yu Chang; Gil Bohrer; William J. Riley; Patrick M. Crill; Ruth K. Varner; Steven J. Blazewicz; et al. (Global Change Biology, 2022)
Permafrost thaw is a major potential feedback source to climate change as it can drive the increased release of greenhouse gases carbon dioxide (CO 2 ) and methane (CH 4 ). This carbon release from the decomposition of thawing soil organic material can be mitigated by increased net primary productivity (NPP) caused by warming, increasing atmospheric CO 2 , and plant community transition. However, the net effect on C storage also depends on how these plant community changes alter plant litter quantity, quality, and decomposition rates. Predicting decomposition rates based on litter quality remains challenging, but a promising new way forward is to incorporate measures of the energetic favorability to soil microbes of plant biomass decomposition. We asked how the variation in one such measure, the nominal oxidation state of carbon (NOSC), interacts with changing quantities of plant material inputs to influence the net C balance of a thawing permafrost peatland. We found: (1) Plant productivity (NPP) increased post‐thaw, but instead of contributing to increased standing biomass, it increased plant biomass turnover via increased litter inputs to soil; (2) Plant litter thermodynamic favorability (NOSC) and decomposition rate both increased post‐thaw, despite limited changes in bulk C:N ratios; (3) these increases caused the higher NPP to cycle more rapidly through both plants and soil, contributing to higher CO 2 and CH 4 fluxes from decomposition. Thus, the increased C‐storage expected from higher productivity was limited and the high global warming potential of CH 4 contributed a net positive warming effect. Although post‐thaw peatlands are currently C sinks due to high NPP offsetting high CO 2 release, this status is very sensitive to the plant community's litter input rate and quality. Integration of novel bioavailability metrics based on litter chemistry, including NOSC, into studies of ecosystem dynamics, is needed to improve the understanding of controls on arctic C stocks under continued ecosystem transition.

Poor relationships between NEON Airborne Observation Platform data and field‐based vegetation traits at a mesic grassland - Stephanie Pau; Jesse B. Nippert; Ryan Slapikas; Daniel Griffith; Seton Bachle; Brent R. Helliker; Rory C. O’Connor; William J. Riley; Christopher J. Still; Marissa Zaricor (Ecology, 2022)
Understanding spatial and temporal variation in plant traits is needed to accurately predict how communities and ecosystems will respond to global change. The National Ecological Observatory Network’s (NEON’s) Airborne Observation Platform (AOP) provides hyperspectral images and associated data products at numerous field sites at 1 m spatial resolution, potentially allowing high‐resolution trait mapping. We tested the accuracy of readily available data products of NEON’s AOP, such as Leaf Area Index (LAI), Total Biomass, Ecosystem Structure (Canopy height model [CHM]), and Canopy Nitrogen, by comparing them to spatially extensive field measurements from a mesic tallgrass prairie. Correlations with AOP data products exhibited generally weak or no relationships with corresponding field measurements. The strongest relationships were between AOP LAI and ground‐measured LAI ( r = 0.32) and AOP Total Biomass and ground‐measured biomass ( r = 0.23). We also examined how well the full reflectance spectra (380–2,500 nm), as opposed to derived products, could predict vegetation traits using partial least‐squares regression (PLSR) models. Among all the eight traits examined, only Nitrogen had a validation of more than 0.25. For all vegetation traits, validation ranged from 0.08 to 0.29 and the range of the root mean square error of prediction (RMSEP) was 14–64%. Our results suggest that currently available AOP‐derived data products should not be used without extensive ground‐based validation. Relationships using the full reflectance spectra may be more promising, although careful consideration of field and AOP data mismatches in space and/or time, biases in field‐based measurements or AOP algorithms, and model uncertainty are needed. Finally, grassland sites may be especially challenging for airborne spectroscopy because of their high species diversity within a small area, mixed functional types of plant communities, and heterogeneous mosaics of disturbance and resource availability. Remote sensing observations are one of the most promising approaches to understanding ecological patterns across space and time. But the opportunity to engage a diverse community of NEON data users will depend on establishing rigorous links with in‐situ field measurements across a diversity of sites.

An introduction to decision science for conservation - Victoria Hemming; Abbey E. Camaclang; Megan S. Adams; Mark Burgman; Katherine Carbeck; Josie Carwardine; Iadine Chadès; Lia Chalifour; Sarah J. Converse; Lindsay N. K. Davidson; Georgia E. Garrard; Riley Finn; et al. (Conservation Biology, 2022)
Biodiversity conservation decisions are difficult, especially when they involve differing values, complex multidimensional objectives, scarce resources, urgency, and considerable uncertainty. Decision science embodies a theory about how to make difficult decisions and an extensive array of frameworks and tools that make that theory practical. We sought to improve conceptual clarity and practical application of decision science to help decision makers apply decision science to conservation problems. We addressed barriers to the uptake of decision science, including a lack of training and awareness of decision science; confusion over common terminology and which tools and frameworks to apply; and the mistaken impression that applying decision science must be time consuming, expensive, and complex. To aid in navigating the extensive and disparate decision science literature, we clarify meaning of common terms: decision science , decision theory , decision analysis , structured decision‐making , and decision‐support tools . Applying decision science does not have to be complex or time consuming; rather, it begins with knowing how to think through the components of a decision utilizing decision analysis (i.e., define the problem, elicit objectives, develop alternatives, estimate consequences, and perform trade‐offs). This is best achieved by applying a rapid‐prototyping approach. At each step, decision‐support tools can provide additional insight and clarity, whereas decision‐support frameworks (e.g., priority threat management and systematic conservation planning) can aid navigation of multiple steps of a decision analysis for particular contexts. We summarize key decision‐support frameworks and tools and describe to which step of a decision analysis, and to which contexts, each is most useful to apply. Our introduction to decision science will aid in contextualizing current approaches and new developments, and help decision makers begin to apply decision science to conservation problems.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Regional trends and drivers of the global methane budget - Ann R. Stavert; Marielle Saunois; Josep G. Canadell; Benjamin Poulter; Robert B. Jackson; Pierre Regnier; Ronny Lauerwald; Peter A. Raymond; George H. Allen; Prabir K. Patra; Peter Bergamaschi; Phillipe Bousquet; et al. (Global Change Biology, 2022)
The ongoing development of the Global Carbon Project (GCP) global methane (CH 4 ) budget shows a continuation of increasing CH 4 emissions and CH 4 accumulation in the atmosphere during 2000–2017. Here, we decompose the global budget into 19 regions (18 land and 1 oceanic) and five key source sectors to spatially attribute the observed global trends. A comparison of top‐down (TD) (atmospheric and transport model‐based) and bottom‐up (BU) (inventory‐ and process model‐based) CH 4 emission estimates demonstrates robust temporal trends with CH 4 emissions increasing in 16 of the 19 regions. Five regions—China, Southeast Asia, USA, South Asia, and Brazil—account for >40% of the global total emissions (their anthropogenic and natural sources together totaling >270 Tg CH 4 yr −1 in 2008–2017). Two of these regions, China and South Asia, emit predominantly anthropogenic emissions (>75%) and together emit more than 25% of global anthropogenic emissions. China and the Middle East show the largest increases in total emission rates over the 2000 to 2017 period with regional emissions increasing by >20%. In contrast, Europe and Korea and Japan show a steady decline in CH 4 emission rates, with total emissions decreasing by ~10% between 2000 and 2017. Coal mining, waste (predominantly solid waste disposal) and livestock (especially enteric fermentation) are dominant drivers of observed emissions increases while declines appear driven by a combination of waste and fossil emission reductions. As such, together these sectors present the greatest risks of further increasing the atmospheric CH 4 burden and the greatest opportunities for greenhouse gas abatement.

Antimicrobial resistance in Clostridioides difficile - Keeley O’Grady; Daniel R. Knight; Thomas V. Riley (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Warm winters and cool springs negatively influence recruitment of Atlantic salmon ( Salmo salar L.) in a southern England chalk stream - Jessica E. Marsh; Rasmus B. Lauridsen; William D. Riley; Olivia M. Simmons; Céline Artero; Luke J. Scott; William R. C. Beaumont; William A. Beaumont; John Davy‐Bowker; Thomas Lecointre; Dylan E. Roberts; Stephen D. Gregory (Journal of Fish Biology, 2021)
Previous work suggests that juvenile salmon recruitment in rain‐fed rivers is negatively influenced by warm and wet winters and cool springs. We tested whether this is generally applicable to a southern England chalk stream characterized by comparatively stable discharges and temperatures. We found that warm spawning and cool emergence temperatures negatively influenced juvenile recruitment between 2015 and 2020. Together these findings suggest an ability to predict juvenile productivity from water temperature records around spawning and fry emergence, thereby allowing time for management interventions in years of unfavourable temperatures.

Identifying dominant environmental predictors of freshwater wetland methane fluxes across diurnal to seasonal time scales - Sara H. Knox; Sheel Bansal; Gavin McNicol; Karina Schafer; Cove Sturtevant; Masahito Ueyama; Alex C. Valach; Dennis Baldocchi; Kyle Delwiche; Ankur R. Desai; Eugenie Euskirchen; Jinxun Liu; et al. (Global Change Biology, 2021)
While wetlands are the largest natural source of methane (CH 4 ) to the atmosphere, they represent a large source of uncertainty in the global CH 4 budget due to the complex biogeochemical controls on CH 4 dynamics. Here we present, to our knowledge, the first multi‐site synthesis of how predictors of CH 4 fluxes (FCH4) in freshwater wetlands vary across wetland types at diel, multiday (synoptic), and seasonal time scales. We used several statistical approaches (correlation analysis, generalized additive modeling, mutual information, and random forests) in a wavelet‐based multi‐resolution framework to assess the importance of environmental predictors, nonlinearities and lags on FCH4 across 23 eddy covariance sites. Seasonally, soil and air temperature were dominant predictors of FCH4 at sites with smaller seasonal variation in water table depth (WTD). In contrast, WTD was the dominant predictor for wetlands with smaller variations in temperature (e.g., seasonal tropical/subtropical wetlands). Changes in seasonal FCH4 lagged fluctuations in WTD by ~17 ± 11 days, and lagged air and soil temperature by median values of 8 ± 16 and 5 ± 15 days, respectively. Temperature and WTD were also dominant predictors at the multiday scale. Atmospheric pressure (PA) was another important multiday scale predictor for peat‐dominated sites, with drops in PA coinciding with synchronous releases of CH 4 . At the diel scale, synchronous relationships with latent heat flux and vapor pressure deficit suggest that physical processes controlling evaporation and boundary layer mixing exert similar controls on CH 4 volatilization, and suggest the influence of pressurized ventilation in aerenchymatous vegetation. In addition, 1‐ to 4‐h lagged relationships with ecosystem photosynthesis indicate recent carbon substrates, such as root exudates, may also control FCH4. By addressing issues of scale, asynchrony, and nonlinearity, this work improves understanding of the predictors and timing of wetland FCH4 that can inform future studies and models, and help constrain wetland CH 4 emissions.

A Synthesis of the Biology and Ecology of Sculpin Species in the Laurentian Great Lakes and Implications for the Adaptive Capacity of the Benthic Ecosystem - Kelly F. Robinson; Charles R. Bronte; David B. Bunnell; Peter T. Euclide; Darryl W. Hondorp; John A. Janssen; Matthew S. Kornis; Derek H. Ogle; Will Otte; Stephen C. Riley; Mark R. Vinson; Shea L. Volkel; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

The Toxicology Investigators Consortium Case Registry—the 2019 Annual Report - Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Kim Aldy; Diane P. Calello; Sharan L. Campleman; Shao Li; Gillian A Beauchamp; Timothy Wiegand; Paul M. Wax; Jeffery Brent; P. A. Akpunonu; et al. (Journal of Medical Toxicology, 2020)

A conceptual framework for the identification and characterization of lacustrine spawning habitats for native lake charr Salvelinus namaycush - Stephen C. Riley; J. Ellen Marsden; Mark S. Ridgway; Christopher P. Konrad; Steven A. Farha; Thomas R. Binder; Trevor A. Middel; Peter C. Esselman; Charles C. Krueger (Environmental Biology of Fishes, 2019)

Urbanization reduces genetic connectivity in bobcats ( Lynx rufus ) at both intra– and interpopulation spatial scales - Christopher P. Kozakiewicz; Christopher P. Burridge; W. Chris Funk; Patricia E. Salerno; Daryl R. Trumbo; Roderick B. Gagne; Erin E. Boydston; Robert N. Fisher; Lisa M. Lyren; Megan K. Jennings; Seth P. D. Riley; Laurel E. K. Serieys; et al. (Molecular Ecology, 2019)
Urbanization is a major factor driving habitat fragmentation and connectivity loss in wildlife. However, the impacts of urbanization on connectivity can vary among species and even populations due to differences in local landscape characteristics, and our ability to detect these relationships may depend on the spatial scale at which they are measured. Bobcats ( Lynx rufus ) are relatively sensitive to urbanization and the status of bobcat populations is an important indicator of connectivity in urban coastal southern California. We genotyped 271 bobcats at 13,520 SNP loci to conduct a replicated landscape resistance analysis in five genetically distinct populations. We tested urban and natural factors potentially influencing individual connectivity in each population separately, as well as study–wide. Overall, landscape genomic effects were most frequently detected at the study–wide spatial scale, with urban land cover (measured as impervious surface) having negative effects and topographic roughness having positive effects on gene flow. The negative effect of urban land cover on connectivity was also evident when populations were analyzed separately despite varying substantially in spatial area and the proportion of urban development, confirming a pervasive impact of urbanization largely independent of spatial scale. The effect of urban development was strongest in one population where stream habitat had been lost to development, suggesting that riparian corridors may help mitigate reduced connectivity in urbanizing areas. Our results demonstrate the importance of replicating landscape genetic analyses across populations and considering how landscape genetic effects may vary with spatial scale and local landscape structure.

Resource allocation to growth or luxury consumption drives mycorrhizal responses - Rohan C. Riley; Timothy R. Cavagnaro; Chris Brien; F. Andrew Smith; Sally E. Smith; Bettina Berger; Trevor Garnett; Rebecca Stonor; Rhiannon K. Schilling; Zhong‐Hua Chen; Jeff R. Powell (Ecology Letters, 2019)
Highly variable phenotypic responses in mycorrhizal plants challenge our functional understanding of plant‐fungal mutualisms. Using non‐invasive high‐throughput phenotyping, we observed that arbuscular mycorrhizal (AM) fungi relieved phosphorus (P) limitation and enhanced growth of Brachypodium distachyon under P‐limited conditions, while photosynthetic limitation under low nitrogen (N) was exacerbated by the fungus. However, these responses were strongly dependent on host genotype: only the faster growing genotype (Bd3‐1) utilised P transferred from the fungus to achieve improved growth under P‐limited conditions. Under low N, the slower growing genotype (Bd21) had a carbon and N surplus that was linked to a less negative growth response compared with the faster growing genotype. These responses were linked to the regulation of N : P stoichiometry, couples resource allocation to growth or luxury consumption in diverse plant lineages. Our results attest strongly to a mechanism in plants by which plant genotype‐specific resource economics drive phenotypic outcomes during AM symbioses.

Use of Seismic Resonance Measurements to Determine the Elastic Modulus of Freestanding Rock Masses - Jeffrey R. Moore; Paul R. Geimer; Riley Finnegan; Michael S. Thorne (Rock Mechanics and Rock Engineering, 2018)

Under what circumstances does the capture and tagging of wild Atlantic salmon Salmo salar smolts affect probability of return as adults? - William D. Riley; Anton T. Ibbotson; Stephen D. Gregory; Ian C. Russell; Rasmus B. Lauridsen; William R. C. Beaumont; Alastair C. Cook; David L. Maxwell (Journal of Fish Biology, 2018)
Adult return rates for wild Atlantic salmon Salmo salar smolts captured in a rotary screw trap and tagged with coded wire (CW) tags were compared with a control group, using detections from passive integrated transponder (PIT) antennae systems over 7 years in a small chalk stream in southern England, U.K. Compared with control smolts, capture and CW‐tagging of experimental smolts affected detected return rates only under certain conditions, with a decreased return probability for smolts caught and tagged following mild winter river temperature anomalies and during the night. Similarly, analysis of the experimental smolts revealed that capture and CW‐tagging following mild winters decreased their probability of return as adults. There were also marginal positive effects of length at PIT‐tagging as parr and length at CW‐tagging as smolts, on individual probability of return as adult. The results support the hypothesis that the effect of procedures involving the capture and tagging of migrating wild S. salar smolts will vary with the circumstances under which they are performed. The implications of the findings are considered in the context of ongoing investigations to derive and report marine return rates for S. salar in support of national and international stock assessments and in developing best practice.

Neural correlates of verbal memory in youth with heavy prenatal alcohol exposure - Lauren A. Gross; Eileen M. Moore; Jeffrey R. Wozniak; Claire D. Coles; Julie A. Kable; Elizabeth R. Sowell; Kenneth L. Jones; Edward P. Riley; Sarah N. Mattson (Brain Imaging and Behavior, 2018)

The pharmacokinetics and metabolism of diclofenac in chimeric humanized and murinized FRG mice - C. E. Wilson; A. P. Dickie; K. Schreiter; R. Wehr; E. M. Wilson; J. Bial; N. Scheer; I. D. Wilson; R. J. Riley (Archives of Toxicology, 2018)

Evidence of repeated long-distance movements by lake charr Salvelinus namaycush in Lake Huron - Stephen C. Riley; Thomas R. Binder; Taaja R. Tucker; Charles C. Krueger (Environmental Biology of Fishes, 2018)

Small-scale intraspecific patterns of adaptive immunogenetic polymorphisms and neutral variation in Lake Superior lake trout - Shauna M. Baillie; Riley R. Hemstock; Andrew M. Muir; Charles C. Krueger; Paul Bentzen (Immunogenetics, 2018)

Functional connectivity abnormalities and associated cognitive deficits in fetal alcohol Spectrum disorders (FASD) - Jeffrey R. Wozniak; Bryon A. Mueller; Sarah N. Mattson; Claire D. Coles; Julie A. Kable; Kenneth L. Jones; Christopher J. Boys; Kelvin O. Lim; Edward P. Riley; Elizabeth R. Sowell (Brain Imaging and Behavior, 2017)

Ventral-aspect radar cross sections and polarization patterns of insects at X band and their relation to size and form - V. A. Drake; J. W. Chapman; K. S. Lim; D. R. Reynolds; J. R. Riley; A. D. Smith (International Journal of Remote Sensing, 2017)

Quantifying the extent of niche areas in the global fleet of commercial ships: the potential for “super-hot spots” of biofouling - Cameron S. Moser; Timothy P. Wier; Matthew R. First; Jonathan F. Grant; Scott C. Riley; Stephanie H. Robbins-Wamsley; Mario N. Tamburri; Gregory M. Ruiz; A. Whitman Miller; Lisa A. Drake (Biological Invasions, 2017)

Islands in the ice stream: were spawning habitats for native salmonids in the Great Lakes created by paleo‐ice streams? - Stephen C Riley; Thomas R Binder; Taaja R Tucker; John Menzies; Nick Eyles; John Janssen; Andrew M Muir; Peter C Esselman; Nigel J Wattrus; Charles C Krueger (Fish and Fisheries, 2017)
Lake trout Salvelinus namaycush , lake whitefish Coregonus clupeaformis and cisco Coregonus artedi are salmonid fishes native to the Laurentian Great Lakes that spawn on rocky substrates in the fall and early winter. After comparing the locations of spawning habitat for these species in the main basin of Lake Huron with surficial substrates and the hypothesized locations of fast‐flowing Late Wisconsinan paleo‐ice streams, we hypothesize that much of the spawning habitat for these species in Lake Huron is the result of deposition and erosion by paleo‐ice streams. This hypothesis may represent a new framework for the identification and protection of spawning habitat for these native species, some of which are currently rare or extirpated in some of the Great Lakes. We further suggest that paleo‐ice streams may have been responsible for the creation of native salmonid spawning habitat elsewhere in the Great Lakes and in other glaciated landscapes.

Towards minimizing transport of aquatic nuisance species in ballast water: Do organisms in different size classes respond uniformly to biocidal treatment? - Matthew R. First; Stephanie H. Robbins-Wamsley; Scott C. Riley; Lisa A. Drake (Biological Invasions, 2016)

First report of E rysipelothrix rhusiopathiae‐ associated septicaemia and histologic changes in cultured A ustralian eels, A nguilla reinhardtii ( S teindachner, 1867) and A . australis ( R ichardson, 1841) - R S‐M Chong; M W Shinwari; M J Amigh; M Aravena‐Roman; T V Riley (Journal of Fish Diseases, 2015)

A blood spot method for detecting fumonisin-induced changes in putative sphingolipid biomarkers in LM/Bc mice and humans - Ronald T. Riley; Jency L. Showker; Christine M. Lee; Cody E. Zipperer; Trevor R. Mitchell; Kenneth A. Voss; Nicholas C. Zitomer; Olga Torres; Jorge Matute; Simon G. Gregory; Allison E. Ashley-Koch; Joyce R. Maddox; et al. (Food Additives & Contaminants: Part A, 2015)

Anticoagulant rodenticides in urban bobcats: exposure, risk factors and potential effects based on a 16-year study - L. E. K. Serieys; T. C. Armenta; J. G. Moriarty; E. E. Boydston; L. M. Lyren; R. H. Poppenga; K. R. Crooks; R. K. Wayne; S. P. D. Riley (Ecotoxicology, 2015)

New insight into the spawning behavior of lake trout, Salvelinus namaycush, from a recovering population in the Laurentian Great Lakes - T. R. Binder; H. T. Thompson; A. M. Muir; S. C. Riley; J. E. Marsden; C. R. Bronte; C. C. Krueger (Environmental Biology of Fishes, 2015)

Associations between CYP19A1 polymorphisms, Native American ancestry, and breast cancer risk and mortality: the Breast Cancer Health Disparities Study - Stephanie D. Boone; Kathy B. Baumgartner; Richard N. Baumgartner; Avonne E. Connor; Christina M. Pinkston; Shesh N. Rai; Elizabeth C. Riley; Lisa M. Hines; Anna R. Giuliano; Esther M. John; Mariana C. Stern; Gabriela Torres-Mejía; et al. (Cancer Causes & Control, 2014)

Development of schooling behaviour during the downstream migration of Atlantic salmon Salmo salar smolts in a chalk stream - W. D. Riley; A. T. Ibbotson; D. L. Maxwell; P. I. Davison; W. R. C. Beaumont; M. J. Ives (Journal of Fish Biology, 2014)
The downstream migratory behaviour of wild Atlantic salmon Salmo salar smolts was monitored using passive integrated transponder ( PIT ) antennae systems over 10 years in the lower reaches of a small chalk stream in southern England, U.K. The timing of smolt movements and the likely occurrence of schooling were investigated and compared to previous studies. In nine of the 10 consecutive years of study, the observed diel downstream patterns of S. salar smolt migration appeared to be synchronized with the onset of darkness. The distribution of time intervals between successive nocturnal detections of PIT ‐tagged smolts was as expected if generated randomly from observed hourly rates. There were, however, significantly more short intervals than expected for smolts detected migrating during the day. For each year from 2006 to 2011, the observed 10th percentile of the daytime intervals was

Clostridium difficile infection diagnosis in a paediatric population: comparison of methodologies - J. Hart; P. Putsathit; D. R. Knight; L. Sammels; T. V. Riley; A. Keil (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

3D imaging provides a high-resolution, volumetric approach for analyzing biofouling - Matthew R. First; Steven A. Policastro; Matthew J. Strom; Scott C. Riley; Stephanie H. Robbins-Wamsley; Lisa A. Drake (Biofouling, 2014)

Expert assessment of vulnerability of permafrost carbon to climate change - E. A. G. Schuur; B. W. Abbott; W. B. Bowden; V. Brovkin; P. Camill; J. G. Canadell; J. P. Chanton; F. S. Chapin; T. R. Christensen; P. Ciais; B. T. Crosby; C. I. Czimczik; et al. (Climatic Change, 2013)

Prevalence of nasal methicillin-resistant Staphylococcus aureus colonization in healthcare workers in a Western Australian acute care hospital - P. E. B. Verwer; J. O. Robinson; G. W. Coombs; T. Wijesuriya; R. J. Murray; H. A. Verbrugh; T. Riley; J. L. Nouwen; K. J. Christiansen (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

RBC-coupled tPA Prevents Whereas tPA Aggravates JNK MAPK-Mediated Impairment of ATP- and Ca-Sensitive K Channel-Mediated Cerebrovasodilation After Cerebral Photothrombosis - William M. Armstead; Kumkum Ganguly; John Riley; Sergei Zaitsev; Douglas B. Cines; Abd Al-Roof Higazi; Vladimir R. Muzykantov (Translational Stroke Research, 2012)

Rats preexposed to MDMA display attenuated responses to its aversive effects in the absence of persistent monoamine depletions - Daniel L. Albaugh; Jennifer A. Rinker; Michael H. Baumann; Jacquelyn R. Sink; Anthony L. Riley (Psychopharmacology, 2011)

Fetal Alcohol Spectrum Disorders: An Overview - Edward P. Riley; M. Alejandra Infante; Kenneth R. Warren (Neuropsychology Review, 2011)

How Research Funding Organizations can Increase Application of Science to Decision-Making - C. Riley; K. Matso; D. Leonard; J. Stadler; D. Trueblood; R. Langan (Coastal Management, 2011)

Lithologic mapping in the Oscar II Coast area, Graham Land, Antarctic Peninsula using ASTER data - C. E. Haselwimmer; T. R. Riley; J. G. Liu (International Journal of Remote Sensing, 2011)

Measures of immune function of wild mice, Mus musculus - STEPHEN R. ABOLINS; MICHAEL J. O. POCOCK; JULIUS C. R. HAFALLA; ELEANOR M. RILEY; MARK E. VINEY (Molecular Ecology, 2011)
The immune function of wild animals has been rather little studied. Wild animals’ immune function may differ from that of laboratory bred animals because of their different environments. This idea follows from the concept of resource partitioning in which animals distribute scarce resources to all aspects of life, including to costly immune responses. A logical extension of this idea is that there may be substantial interindividual variation in the immune function of wild animals. To begin to investigate this, we compared the immune function of a laboratory bred mouse strain (C57BL/6, a widely used mouse strain that makes potent immune responses) and wild caught Mus musculus. We found that by most measures of immune function, the wild caught mice had greater immune function. Specifically, wild mice had greater concentrations and more avid antigen‐specific IgG responses, as well as higher concentrations of total IgG and IgE, compared with those laboratory bred mice. Moreover, flow cytometric analysis showed a comparatively greater overall level of activation of the cells of the immune system in wild mice. Lastly, we observed that immune function was substantially more variable among wild caught mice than among the laboratory bred mice. The next research challenge is to understand which aspects of an individual animal’s life determine its immune function.

Applicability of Penicillium chrysogenum rheological correlations to broths of other fungal strains - G. L. Riley; C. R. Thomas (Biotechnology Letters, 2010)

Probing S4 and S5 segment proximity in mammalian hyperpolarization-activated HCN channels by disulfide bridging and Cd2+ coordination - Damian C. Bell; Harma K. Turbendian; Matthew T. Valley; Lei Zhou; John H. Riley; Steven A. Siegelbaum; Gareth R. Tibbs (Pflügers Archiv - European Journal of Physiology, 2009)

Movements of brown smoothhounds, Mustelus henlei, in Tomales Bay, California - Brent R. Campos; Maxfield A. Fish; Gardner Jones; Rebecca W. Riley; Peter J. Allen; Peter A. Klimley; Joseph J. Cech; John T. Kelly (Environmental Biology of Fishes, 2009)

Adult returns from Atlantic salmon, Salmo salar , parr autumn migrants - W. D. RILEY; A. T. IBBOTSON; W. R. C. BEAUMONT (Fisheries Management and Ecology, 2009)

Do feral buffalo ( Bubalus bubalis ) explain the increase of woody cover in savannas of Kakadu National Park, Australia? - D. M. J. S. Bowman; J. E. Riley; G. S. Boggs; C. E. R. Lehmann; L. D. Prior (Journal of Biogeography, 2008)
Aim To study changes in woody vegetation in both floodplains and eucalypt savanna over a 40‐year period using multi‐temporal spatial analysis of variation in density of a large introduced herbivore, the Asian water buffalo ( Bubalus bubalis ). Feral buffalo built up to high densities in the study area until c. 1985, after which a control programme almost eliminated the animals. From 1990, low densities of managed buffalo were maintained inside an enclosure. We compared trends in woody vegetation when buffalo were high‐density feral, low‐density managed or absent. Location The study area was located in and around a 116‐km 2 buffalo enclosure inside Kakadu National Park, in monsoonal northern Australia. Methods We analysed sequences of digitized and geo‐rectified aerial photographs, acquired in 1964, 1975, 1984, 1991 and 2004, to chart changes in woody cover on the floodplain and in the savanna. On the floodplain we assessed whether trees were present at these times at 14,568 points, and buffalo density was estimated from the density of animal tracks. In the savanna we estimated woody cover at pre‐selected sites. Generalized linear modelling was used to analyse changes in woody vegetation, using elevation and presence of woody vegetation in neighbouring points on the floodplain, and buffalo regime and initial woody cover in the savanna . Results Changes in animal track density reflected park‐wide historical estimates of buffalo numbers. Tree cover increased in both floodplain and savanna, but this was only weakly related to buffalo density. The best predictor of whether a floodplain cell converted from treeless to woody, or the converse, was the woodiness of neighbouring vegetation. There was slightly less thickening with high buffalo densities. In savanna, low densities of managed buffalo were weakly associated with increases in tree cover relative to either high densities of feral buffalo or no buffalo. Main conclusions Our study indicates that buffalo are not a major driver of floodplain and eucalypt savanna dynamics. Rather, the observed increase in woody cover in both savanna and flood plains concords with regional trends and may be related to increased atmospheric CO 2 , increasing rainfall and changing fire regimes during the study period.

Essential value of cocaine and food in rats: tests of the exponential model of demand - Chesley J. Christensen; Alan Silberberg; Steven R. Hursh; Mary E. Huntsberry; Anthony L. Riley (Psychopharmacology, 2008)

Structural and spectroscopic studies of a model for catechol oxidase - Sarah J. Smith; Christopher J. Noble; Randahl C. Palmer; Graeme R. Hanson; Gerhard Schenk; Lawrence R. Gahan; Mark J. Riley (JBIC Journal of Biological Inorganic Chemistry, 2008)

Thymosin β4 and Ac-SDKP: Tools to mend a broken heart - Alex Rossdeutsch; Nicola Smart; Paul R. Riley (Journal of Molecular Medicine, 2008)

Probing the role of the divalent metal ion in uteroferrin using metal ion replacement and a comparison to isostructural biomimetics - Gerhard Schenk; Rosely A. Peralta; Suzana Cimara Batista; Adailton J. Bortoluzzi; Bruno Szpoganicz; Andrew K. Dick; Paul Herrald; Graeme R. Hanson; Robert K. Szilagyi; Mark J. Riley; Lawrence R. Gahan; Ademir Neves (JBIC Journal of Biological Inorganic Chemistry, 2007)

Thymosin β4 and angiogenesis: modes of action and therapeutic potential - Nicola Smart; Alex Rossdeutsch; Paul R. Riley (Angiogenesis, 2007)

The reaction mechanism of the Ga(III)Zn(II) derivative of uteroferrin and corresponding biomimetics - Sarah J. Smith; Annelise Casellato; Kieran S. Hadler; Nataša Mitić; Mark J. Riley; Adailton J. Bortoluzzi; Bruno Szpoganicz; Gerhard Schenk; Ademir Neves; Lawrence R. Gahan (JBIC Journal of Biological Inorganic Chemistry, 2007)

Impact of trapping and tagging on the timing of continued seaward migration of wild Atlantic salmon, Salmo salar , smolts - W. D. Riley; A. Moore; I. C. Russell; I. C. Davidson; R. J. Cove; M. J. Ives (Fisheries Management and Ecology, 2007)

Evidence for an autumn downstream migration and the subsequent estuarine residence of 0+ year juvenile Atlantic salmon Salmo salar L., in England - A. C. Pinder; W. D. Riley; A. T. Ibbotson; W. R. C. Beaumont (Journal of Fish Biology, 2007)
The use of passive integrated transponder technology facilitated the first observations of the autumn migration of 0+ year Atlantic salmon Salmo salar parr into tidal rearing habitats in the U.K. The quality of these habitats in relation to smolt production and the ecological significance of this alternative life‐history strategy are presently not understood.

Hydraulische Modellierung und die Ermittlung des repräsentativen Elementarvolumens (REV) im Kluftgestein - P. Blum; R. Mackay; M.S. Riley; J.L. Knight (Grundwasser, 2007)

Comparison of Nitrate Levels in Raw Water and Finished Water from Historical Monitoring Data on Iowa Municipal Drinking Water Supplies - Peter J. Weyer; Brian J. Smith; Zhen-Fang Feng; Jiji R. Kantamneni; David G. Riley (Environmental Monitoring and Assessment, 2006)

Combining meteorology, eddy fluxes, isotope measurements, and modeling to understand environmental controls of carbon isotope discrimination at the canopy scale - J. N. ARANIBAR; J. A. BERRY; W. J. RILEY; D. E. PATAKI; B. E. LAW; J. R. EHLERINGER (Global Change Biology, 2006)
Estimates of terrestrial carbon isotope discrimination are useful to quantify the terrestrial carbon sink. Carbon isotope discrimination by terrestrial ecosystems may vary on seasonal and interannual time frames, because it is affected by processes (e.g. photosynthesis, stomatal conductance, and respiration) that respond to variable environmental conditions (e.g. air humidity, temperature, light). In this study, we report simulations of the temporal variability of canopy‐scale C 3 photosynthetic carbon isotope discrimination obtained with an ecophysiologically based model (ISOLSM) designed for inclusion in global models. ISOLSM was driven by half‐hourly meteorology, and parameterized with eddy covariance measurements of carbon and energy fluxes and foliar carbon isotope ratios from a pine forest in Metolius (OR). Comparing simulated carbon and energy fluxes with observations provided a range of parameter values that optimized the simulated fluxes. We found that the sensitivity of photosynthetic carbon isotope discrimination to the slope of the stomatal conductance equation ( m , Ball–Berry constant) provided an additional constraint to the model, reducing the wide parameter space obtained from the fluxes alone. We selected values of m that resulted in similar simulated long‐term discrimination as foliar isotope ratios measured at the site. The model was tested with 13 C measurements of ecosystem ( δ R ) and foliar ( δ f ) respiration. The daily variability of simulated 13 C values of assimilated carbon ( δ A ) was similar to that of observed δ f , and higher than that of observed and simulated δ R . We also found similar relationships between environmental factors (i.e. vapor pressure deficit) and simulated δ R as measured in ecosystem surveys of δ R . Therefore, ISOLSM reasonably simulated the short‐term variability of δ A controlled by atmospheric conditions at the canopy scale, which can be useful to estimate the variability of terrestrial isotope discrimination. Our study also shows that including the capacity to simulate carbon isotope discrimination, together with simple ecosystem isotope measurements, can provide a useful constraint to land surface and carbon balance models.

A new heterobinuclear FeIIICuII complex with a single terminal FeIII–O(phenolate) bond. Relevance to purple acid phosphatases and nucleases - Mauricio Lanznaster; Ademir Neves; Adailton J. Bortoluzzi; Veronika V. E. Aires; Bruno Szpoganicz; Hernán Terenzi; Patricia Cardoso Severino; Julie M. Fuller; Simon C. Drew; Lawrence R. Gahan; Graeme R. Hanson; Mark J. Riley; et al. (JBIC Journal of Biological Inorganic Chemistry, 2005)

Paleokarst and reservoir porosity in the Ordovician Beekmantown Dolomite of the central appalachian basin - Richard Smosna; Kathy R. Bruner; Ronald A. Riley (Carbonates and Evaporites, 2005)

Phytoecdysteroids: A Novel Defense Against Plant-Parasitic Nematodes - Imelda R. Soriano; Ian T. Riley; Mark J. Potter; William S. Bowers (Journal of Chemical Ecology, 2004)

A comprehensive and systematic approach to developing and documenting conceptual models of contaminant release and migration at the Hanford Site - G. V. Last; V. J. Rohay; F. J. Schelling; A. L. Bunn; M. A. Delamare; R. L. Dirkes; R. D. Hildebr; J. G. Morse; B. A. Napier; R. G. Riley; L. Soler; P. D. Thorne (Stochastic Environmental Research and Risk Assessment, 2004)

18 O composition of CO 2 and H 2 O ecosystem pools and fluxes in a tallgrass prairie: Simulations and comparisons to measurements - William J. Riley; Christopher J. Still; Brent R. Helliker; Miguel Ribas‐Carbo; Joseph A. Berry (Global Change Biology, 2003)
In this paper we describe measurements and modeling of 18 O in CO 2 and H 2 O pools and fluxes at a tallgrass prairie site in Oklahoma. We present measurements of the δ 18 O value of leaf water, depth‐resolved soil water, atmospheric water vapor, and Keeling plot δ 18 O intercepts for net soil‐surface CO 2 and ecosystem CO 2 and H 2 O fluxes during three periods of the 2000 growing season. Daytime discrimination against C 18 OO, as calculated from measured above‐canopy CO 2 and δ 18 O gradients, is also presented. To interpret the isotope measurements, we applied an integrated land‐surface and isotope model (ISOLSM) that simulates ecosystem H 2 18 O and C 18 OO stocks and fluxes. ISOLSM accurately predicted the measured isotopic composition of ecosystem water pools and the δ 18 O value of net ecosystem CO 2 and H 2 O fluxes. Simulations indicate that incomplete equilibration between CO 2 and H 2 O within C 4 plant leaves can have a substantial impact on ecosystem discrimination. Diurnal variations in the δ 18 O value of above‐canopy vapor had a small impact on the predicted δ 18 O value of ecosystem water pools, although sustained differences had a large impact. Diurnal variations in the δ 18 O value of above‐canopy CO 2 substantially affected the predicted ecosystem discrimination. Leaves dominate the ecosystem 18 O‐isoflux in CO 2 during the growing season, while the soil contribution is relatively small and less variable. However, interpreting daytime measurements of ecosystem C 18 OO fluxes requires accurate predictions of both soil and leaf 18 O‐isofluxes.

Is there a ?forest filter effect? for organic pollutants? - R. L. Maddalena; T. E. McKone; W. J. Riley (Stochastic Environmental Research and Risk Assessment, 2003)

Genetic population structure of the white sifaka ( Propithecus verreauxi verreauxi ) at Beza Mahafaly Special Reserve, southwest Madagascar (1992–2001) - Richard R. Lawler; Alison F. Richard; Margaret A. Riley (Molecular Ecology, 2003)
Gene flow within and between social groups is contingent on behaviourally mediated patterns of mating and dispersal. To understand how these patterns affect the genetic structure of primate populations, long‐term data are required. In this study, we analyse 10 years of demographic and genetic data from a wild lemur population ( Propithecus verreauxi verreauxi ) at Beza Mahafaly Special Reserve, southwest Madagascar. Our goal is to specify how patterns of mating and dispersal determine kinship and genetic diversity among animals in the population. Specifically, we use microsatellite, parentage, and census data to obtain estimates of genetic subdivision ( F ST ), within group homozygosity ( F IS ), and relatedness ( r ) within and among social groups in the population. We analyse different classes of individuals (i.e. adults, offspring, males, females) separately in order to discern which classes most strongly influence aspects of population structure. Microsatellite data reveal that, across years, offspring are consistently more heterozygous than expected within social groups ( F IS mean = −0.068) while adults show both positive and negative deviations from expected genotypic frequencies within groups ( F IS mean = 0.003). Offspring cohorts are more genetically subdivided than adults ( F ST mean = 0.108 vs. 0.052) and adult females are more genetically subdivided than adult males ( F ST mean = 0.098 vs. 0.046). As the proportion of females in social groups increases, the proportion of offspring sired by resident males decreases. Offspring are characterized by a heterozygote excess as resident males (vs. nonresident males) sire the majority of offspring within groups. We link these genetic data to patterns of female philopatry, male dispersal, exogamy, and offspring sex‐ratio. Overall, these data reveal how mating and dispersal tactics influence the genetic population structure in this species.

Nitrogen dynamics of grass as affected by N input regimes, soil texture and climate: lysimeter measurements and simulations - Audun Korsaeth; Lars R. Bakken; Hugh Riley (Nutrient Cycling in Agroecosystems, 2003)

Headwater stream response to grassland agricultural development in New Zealand - Ralph H. Riley; Colin R. Townsend; Dev K. Niyogi; Chris A. Arbuckle; Kathi A. Peacock (New Zealand Journal of Marine and Freshwater Research, 2003)
Agricultural development of native grasslands may change stream physico‐chemistry in ways that provide both subsidies and stresses to the system. The aims of this study were to determine: (1) which physico‐chemical parameters respond most strongly to agricultural development; (2) how biodiversity, community composition, and food‐web structure responded to these changes; and (3) to determine the balance between negative and positive impacts of these subsidies and stresses based on the analysis of 18 headwater streams. Developed pasture streams had increased nutrient loading, alterations to streamside vegetation, increased fine sediment composition, and lower moss coverage of stream‐beds than undeveloped or lightly grazed native grassland catchments (which could not be distinguished from one another). These differences were associated with higher numbers of macroinvertebrate taxa and higher numbers of macroinvertebrates indicating that the net effects of these subsidies and stresses associated with agricultural development were positive within these headwater stream reaches.

Development of a Generalized, Quantitative Physicochemical Model of CYP3A4 Inhibition for Use in Early Drug Discovery - R. J. Riley; A. J. Parker; S. Trigg; C. N. Manners (Pharmaceutical Research, 2001)

A hemizygous short tandem repeat polymorphism 3′ to the human phosphoglycerate kinase gene - Donald E. Riley; In R. Cho; John N. Krieger (Molecular Biology Reports, 1999)

Harmonic Radar as a Means of Tracking the Pheromone-Finding and Pheromone-Following Flight of Male Moths - J. R. Riley; P. Valeur; A. D. Smith; D. R. Reynolds; G. M. Poppy; C. Löfstedt (Journal of Insect Behavior, 1998)

Assay for Toxic Chemicals Using Bacteria - J. L. Botsford; J. Rivera; J. Navarez; R. Riley; T. Wright; R. Baker (Bulletin of Environmental Contamination and Toxicology, 1997)

Drilling fluids and the arctic tundra of Alaska: Assessing contamination of wetlands habitat and the toxicity to aquatic invertebrates and fish - Daniel F. Woodward; Elaine Snyder-Conn; Robert G. Riley; Thomas R. Garland (Archives of Environmental Contamination and Toxicology, 1988)

Accumulation, sublethal effects, and safe concentration of a refined oil as evaluated with cutthroat trout - D. F. Woodward; R. G. Riley; C. E. Smith (Archives of Environmental Contamination and Toxicology, 1983)

Petroleum hydrocarbon concentrations in a salmonid stream contaminated by oil field discharge water and effects on macrobenthos - D. F. Woodward; R. G. Riley (Archives of Environmental Contamination and Toxicology, 1983)

Insecticides for control of potato tuberworm and green peach aphid on potatoes in California - O. G. Bacon; N. F. McCalley; W. D. Riley; R. H. James (American Journal of Potato Research, 1972)